Variational approaches to quantum impurities: from the Fröhlich polaron to the angulon - Li, Xiang; Bighin, Giacomo; Yakaboylu, Enderalp; Lemeshko, Mikhail (Molecular Physics)
Problems involving quantum impurities, in which one or a few particles are interacting with a macroscopic environment, represent a pervasive paradigm, spanning across atomic, molecular, and condensed-matter physics. In this paper we introduce new variational approaches to quantum impurities and apply them to the Fröhlich polaron–a quasiparticle formed out of an electron (or other point-like impurity) in a polar medium, and to the angulon–a quasiparticle formed out of a rotating molecule in a bosonic bath. We benchmark these approaches against established theories, evaluating their accuracy as a function of the impurity-bath coupling.

3-manifold triangulations with small treewidth - Huszár, Kristóf; Spreer, Jonathan (35th International Symposium on Computational Geometry)
Motivated by fixed-parameter tractable (FPT) problems in computational topology, we consider the treewidth tw(M) of a compact, connected 3-manifold M, defined to be the minimum treewidth of the face pairing graph of any triangulation T of M. In this setting the relationship between the topology of a 3-manifold and its treewidth is of particular interest. First, as a corollary of work of Jaco and Rubinstein, we prove that for any closed, orientable 3-manifold M the treewidth tw(M) is at most 4g(M)-2, where g(M) denotes Heegaard genus of M. In combination with our earlier work with Wagner, this yields that for non-Haken manifolds the Heegaard genus and the treewidth are within a constant factor. Second, we characterize all 3-manifolds of treewidth one: These are precisely the lens spaces and a single other Seifert fibered space. Furthermore, we show that all remaining orientable Seifert fibered spaces over the 2-sphere or a non-orientable surface have treewidth two. In particular, for every spherical 3-manifold we exhibit a triangulation of treewidth at most two. Our results further validate the parameter of treewidth (and other related parameters such as cutwidth or congestion) to be useful for topological computing, and also shed more light on the scope of existing FPT-algorithms in the field.
Keywords: computational 3-manifold topology; fixed-parameter tractability; layered triangulations; structural graph theory; treewidth; cutwidth; Heegaard genus

On the treewidth of triangulated 3-manifolds - Huszár, Kristóf; Spreer, Jonathan; Wagner, Uli (Journal of Computational Geometry)
In graph theory, as well as in 3-manifold topology, there exist several width-type parameters to describe how "simple" or "thin" a given graph or 3-manifold is. These parameters, such as pathwidth or treewidth for graphs, or the concept of thin position for 3-manifolds, play an important role when studying algorithmic problems; in particular, there is a variety of problems in computational 3-manifold topology - some of them known to be computationally hard in general - that become solvable in polynomial time as soon as the dual graph of the input triangulation has bounded treewidth. In view of these algorithmic results, it is natural to ask whether every 3-manifold admits a triangulation of bounded treewidth. We show that this is not the case, i.e., that there exists an infinite family of closed 3-manifolds not admitting triangulations of bounded pathwidth or treewidth (the latter implies the former, but we present two separate proofs). We derive these results from work of Agol, of Scharlemann and Thompson, and of Scharlemann, Schultens and Saito by exhibiting explicit connections between the topology of a 3-manifold M on the one hand and width-type parameters of the dual graphs of triangulations of M on the other hand, answering a question that had been raised repeatedly by researchers in computational 3-manifold topology. In particular, we show that if a closed, orientable, irreducible, non-Haken 3-manifold M has a triangulation of treewidth (resp. pathwidth) k then the Heegaard genus of M is at most 18(k+1) (resp. 4(3k+1)).

Cooperative ordering of treadmilling filaments in cytoskeletal networks of FtsZ and its crosslinker ZapA - Dos Santos Caldas, Paulo R; Lopez Pelegrin, Maria D; Pearce, Daniel J. G.; Budanur, Nazmi B; Brugués, Jan; Loose, Martin (Nature Communications)
During bacterial cell division, the tubulin-homolog FtsZ forms a ring-like structure at the center of the cell. This Z-ring not only organizes the division machinery, but treadmilling of FtsZ filaments was also found to play a key role in distributing proteins at the division site. What regulates the architecture, dynamics and stability of the Z-ring is currently unknown, but FtsZ-associated proteins are known to play an important role. Here, using an in vitro reconstitution approach, we studied how the well-conserved protein ZapA affects FtsZ treadmilling and filament organization into large-scale patterns. Using high-resolution fluorescence microscopy and quantitative image analysis, we found that ZapA cooperatively increases the spatial order of the filament network, but binds only transiently to FtsZ filaments and has no effect on filament length and treadmilling velocity. Together, our data provides a model for how FtsZ-associated proteins can increase the precision and stability of the bacterial cell division machinery in a switch-like manner.

Population structure determines the tradeoff between fixation probability and fixation time - Tkadlec, Josef; Pavlogiannis, Andreas; Chatterjee, Krishnendu; Nowak, Martin A. (Communications Biology)
The rate of biological evolution depends on the fixation probability and on the fixation time of new mutants. Intensive research has focused on identifying population structures that augment the fixation probability of advantageous mutants. But these amplifiers of natural selection typically increase fixation time. Here we study population structures that achieve a tradeoff between fixation probability and time. First, we show that no amplifiers can have an asymptotically lower absorption time than the well-mixed population. Then we design population structures that substantially augment the fixation probability with just a minor increase in fixation time. Finally, we show that those structures enable higher effective rate of evolution than the well-mixed population provided that the rate of generating advantageous mutants is relatively low. Our work sheds light on how population structure affects the rate of evolution. Moreover, our structures could be useful for lab-based, medical, or industrial applications of evolutionary optimization.

Value-centric dynamic partial order reduction - Chatterjee, Krishnendu; Pavlogiannis, Andreas; Toman, Viktor (Proceedings of the 34th ACM International Conference on Object-Oriented Programming, Systems, Languages, and Applications)
The verification of concurrent programs remains an open challenge, as thread interaction has to be accounted for, which leads to state-space explosion. Stateless model checking battles this problem by exploring traces rather than states of the program. As there are exponentially many traces, dynamic partial-order reduction (DPOR) techniques are used to partition the trace space into equivalence classes, and explore a few representatives from each class. The standard equivalence that underlies most DPOR techniques is the happens-before equivalence, however recent works have spawned a vivid interest towards coarser equivalences. The efficiency of such approaches is a product of two parameters: (i) the size of the partitioning induced by the equivalence, and (ii) the time spent by the exploration algorithm in each class of the partitioning. In this work, we present a new equivalence, called value-happens-before and show that it has two appealing features. First, value-happens-before is always at least as coarse as the happens-before equivalence, and can be even exponentially coarser. Second, the value-happens-before partitioning is efficiently explorable when the number of threads is bounded. We present an algorithm called value-centric DPOR (VCDPOR), which explores the underlying partitioning using polynomial time per class. Finally, we perform an experimental evaluation of VCDPOR on various benchmarks, and compare it against other state-of-the-art approaches. Our results show that value-happens-before typically induces a significant reduction in the size of the underlying partitioning, which leads to a considerable reduction in the running time for exploring the whole partitioning.
Keywords: safety; risk; reliability and quality; software

Efficiency guarantees for parallel incremental algorithms under relaxed schedulers - Alistarh, Dan-Adrian; Nadiradze, Giorgi; Koval, Nikita (31st ACM Symposium on Parallelism in Algorithms and Architectures)
Several classic problems in graph processing and computational geometry are solved via incremental algorithms, which split computation into a series of small tasks acting on shared state, which gets updated progressively. While the sequential variant of such algorithms usually specifies a fixed (but sometimes random) order in which the tasks should be performed, a standard approach to parallelizing such algorithms is to relax this constraint to allow for out-of-order parallel execution. This is the case for parallel implementations of Dijkstra's single-source shortest-paths (SSSP) algorithm, and for parallel Delaunay mesh triangulation. While many software frameworks parallelize incremental computation in this way, it is still not well understood whether this relaxed ordering approach can still provide any complexity guarantees. In this paper, we address this problem, and analyze the efficiency guarantees provided by a range of incremental algorithms when parallelized via relaxed schedulers. We show that, for algorithms such as Delaunay mesh triangulation and sorting by insertion, schedulers with a maximum relaxation factor of k in terms of the maximum priority inversion allowed will introduce a maximum amount of wasted work of O(łog n poly(k)), where n is the number of tasks to be executed. For SSSP, we show that the additional work is O(poly(k), dmax / wmin), where dmax is the maximum distance between two nodes, and wmin is the minimum such distance. In practical settings where n >> k, this suggests that the overheads of relaxation will be outweighed by the improved scalability of the relaxed scheduler. On the negative side, we provide lower bounds showing that certain algorithms will inherently incur a non-trivial amount of wasted work due to scheduler relaxation, even for relatively benign relaxed schedulers.

A comparison of the transport kinetics of glycine transporter 1 and glycine transporter 2 - Erdem, Fatma Asli; Ilic, Marija; Koppensteiner, Peter; Gołacki, Jakub; Lubec, Gert; Freissmuth, Michael; Sandtner, Walter (The Journal of General Physiology)
Transporters of the solute carrier 6 (SLC6) family translocate their cognate substrate together with Na+ and Cl−. Detailed kinetic models exist for the transporters of GABA (GAT1/SLC6A1) and the monoamines dopamine (DAT/SLC6A3) and serotonin (SERT/SLC6A4). Here, we posited that the transport cycle of individual SLC6 transporters reflects the physiological requirements they operate under. We tested this hypothesis by analyzing the transport cycle of glycine transporter 1 (GlyT1/SLC6A9) and glycine transporter 2 (GlyT2/SLC6A5). GlyT2 is the only SLC6 family member known to translocate glycine, Na+, and Cl− in a 1:3:1 stoichiometry. We analyzed partial reactions in real time by electrophysiological recordings. Contrary to monoamine transporters, both GlyTs were found to have a high transport capacity driven by rapid return of the empty transporter after release of Cl− on the intracellular side. Rapid cycling of both GlyTs was further supported by highly cooperative binding of cosubstrate ions and substrate such that their forward transport mode was maintained even under conditions of elevated intracellular Na+ or Cl−. The most important differences in the transport cycle of GlyT1 and GlyT2 arose from the kinetics of charge movement and the resulting voltage-dependent rate-limiting reactions: the kinetics of GlyT1 were governed by transition of the substrate-bound transporter from outward- to inward-facing conformations, whereas the kinetics of GlyT2 were governed by Na+ binding (or a related conformational change). Kinetic modeling showed that the kinetics of GlyT1 are ideally suited for supplying the extracellular glycine levels required for NMDA receptor activation.

Structures of respiratory supercomplex I+III2 reveal functional and conformational crosstalk - Letts, James A; Fiedorczuk, Karol; Degliesposti, Gianluca; Skehel, Mark; Sazanov, Leonid A (Molecular Cell)
The mitochondrial electron transport chain complexes are organized into supercomplexes (SCs) of defined stoichiometry, which have been proposed to regulate electron flux via substrate channeling. We demonstrate that CoQ trapping in the isolated SC I+III2 limits complex (C)I turnover, arguing against channeling. The SC structure, resolved at up to 3.8 Å in four distinct states, suggests that CoQ oxidation may be rate limiting because of unequal access of CoQ to the active sites of CIII2. CI shows a transition between “closed” and “open” conformations, accompanied by the striking rotation of a key transmembrane helix. Furthermore, the state of CI affects the conformational flexibility within CIII2, demonstrating crosstalk between the enzymes. CoQ was identified at only three of the four binding sites in CIII2, suggesting that interaction with CI disrupts CIII2 symmetry in a functionally relevant manner. Together, these observations indicate a more nuanced functional role for the SCs.

NetPyNE, a tool for data-driven multiscale modeling of brain circuits - Dura-Bernal, Salvador; Suter, Benjamin; Gleeson, Padraig; Cantarelli, Matteo; Quintana, Adrian; Rodriguez, Facundo; Kedziora, David J; Chadderdon, George L; Kerr, Cliff C; Neymotin, Samuel A; McDougal, Robert A; Hines, Michael; et al. (eLife)
Biophysical modeling of neuronal networks helps to integrate and interpret rapidly growing and disparate experimental datasets at multiple scales. The NetPyNE tool (www.netpyne.org) provides both programmatic and graphical interfaces to develop data-driven multiscale network models in NEURON. NetPyNE clearly separates model parameters from implementation code. Users provide specifications at a high level via a standardized declarative language, for example connectivity rules, to create millions of cell-to-cell connections. NetPyNE then enables users to generate the NEURON network, run efficiently parallelized simulations, optimize and explore network parameters through automated batch runs, and use built-in functions for visualization and analysis – connectivity matrices, voltage traces, spike raster plots, local field potentials, and information theoretic measures. NetPyNE also facilitates model sharing by exporting and importing standardized formats (NeuroML and SONATA). NetPyNE is already being used to teach computational neuroscience students and by modelers to investigate brain regions and phenomena.

Early sex-chromosome evolution in the diploid dioecious plant Mercurialis annua - Veltsos, Paris; Ridout, Kate E.; Toups, Melissa A; González-Martínez, Santiago C.; Muyle, Aline; Emery, Olivier; Rastas, Pasi; Hudzieczek, Vojtech; Hobza, Roman; Vyskot, Boris; Marais, Gabriel A. B.; Filatov, Dmitry A.; et al. (Genetics)
Suppressed recombination allows divergence between homologous sex chromosomes and the functionality of their genes. Here, we reveal patterns of the earliest stages of sex-chromosome evolution in the diploid dioecious herb Mercurialis annua on the basis of cytological analysis, de novo genome assembly and annotation, genetic mapping, exome resequencing of natural populations, and transcriptome analysis. The genome assembly contained 34,105 expressed genes, of which 10,076 were assigned to linkage groups. Genetic mapping and exome resequencing of individuals across the species range both identified the largest linkage group, LG1, as the sex chromosome. Although the sex chromosomes of M. annua are karyotypically homomorphic, we estimate that about one-third of the Y chromosome, containing 568 transcripts and spanning 22.3 cM in the corresponding female map, has ceased recombining. Nevertheless, we found limited evidence for Y-chromosome degeneration in terms of gene loss and pseudogenization, and most X- and Y-linked genes appear to have diverged in the period subsequent to speciation between M. annua and its sister species M. huetii, which shares the same sex-determining region. Taken together, our results suggest that the M. annua Y chromosome has at least two evolutionary strata: a small old stratum shared with M. huetii, and a more recent larger stratum that is probably unique to M. annua and that stopped recombining ∼1 MYA. Patterns of gene expression within the nonrecombining region are consistent with the idea that sexually antagonistic selection may have played a role in favoring suppressed recombination.

Transient localization of the Arp2/3 complex initiates neuronal dendrite branching in vivo - Stürner, Tomke; Tatarnikova, Anastasia; Müller, Jan; Schaffran, Barbara; Cuntz, Hermann; Zhang, Yun; Nemethova, Maria; Bogdan, Sven; Small, Vic; Tavosanis, Gaia (Development)
The formation of neuronal dendrite branches is fundamental for the wiring and function of the nervous system. Indeed, dendrite branching enhances the coverage of the neuron's receptive field and modulates the initial processing of incoming stimuli. Complex dendrite patterns are achieved in vivo through a dynamic process of de novo branch formation, branch extension and retraction. The first step towards branch formation is the generation of a dynamic filopodium-like branchlet. The mechanisms underlying the initiation of dendrite branchlets are therefore crucial to the shaping of dendrites. Through in vivo time-lapse imaging of the subcellular localization of actin during the process of branching of Drosophila larva sensory neurons, combined with genetic analysis and electron tomography, we have identified the Actin-related protein (Arp) 2/3 complex as the major actin nucleator involved in the initiation of dendrite branchlet formation, under the control of the activator WAVE and of the small GTPase Rac1. Transient recruitment of an Arp2/3 component marks the site of branchlet initiation in vivo. These data position the activation of Arp2/3 as an early hub for the initiation of branchlet formation.

Graph planning with expected finite horizon - Chatterjee, Krishnendu; Doyen, Laurent (34th Annual ACM/IEEE Symposium on Logic in Computer Science)
Graph planning gives rise to fundamental algorithmic questions such as shortest path, traveling salesman problem, etc. A classical problem in discrete planning is to consider a weighted graph and construct a path that maximizes the sum of weights for a given time horizon T. However, in many scenarios, the time horizon is not fixed, but the stopping time is chosen according to some distribution such that the expected stopping time is T. If the stopping time distribution is not known, then to ensure robustness, the distribution is chosen by an adversary, to represent the worst-case scenario. A stationary plan for every vertex always chooses the same outgoing edge. For fixed horizon or fixed stopping-time distribution, stationary plans are not sufficient for optimality. Quite surprisingly we show that when an adversary chooses the stopping-time distribution with expected stopping time T, then stationary plans are sufficient. While computing optimal stationary plans for fixed horizon is NP-complete, we show that computing optimal stationary plans under adversarial stopping-time distribution can be achieved in polynomial time. Consequently, our polynomial-time algorithm for adversarial stopping time also computes an optimal plan among all possible plans.

Finite-size scaling of the photon-blockade breakdown dissipative quantum phase transition - Vukics, A.; Dombi, A.; Fink, Johannes M; Domokos, P. (Quantum)
We prove that the observable telegraph signal accompanying the bistability in the photon-blockade-breakdown regime of the driven and lossy Jaynes–Cummings model is the finite-size precursor of what in the thermodynamic limit is a genuine first-order phase transition. We construct a finite-size scaling of the system parameters to a well-defined thermodynamic limit, in which the system remains the same microscopic system, but the telegraph signal becomes macroscopic both in its timescale and intensity. The existence of such a finite-size scaling completes and justifies the classification of the photon-blockade-breakdown effect as a first-order dissipative quantum phase transition.

Map inference via block-coordinate Frank-Wolfe algorithm - Swoboda, Paul; Kolmogorov, Vladimir (Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition)
We present a new proximal bundle method for Maximum-A-Posteriori (MAP) inference in structured energy minimization problems. The method optimizes a Lagrangean relaxation of the original energy minimization problem using a multi plane block-coordinate Frank-Wolfe method that takes advantage of the specific structure of the Lagrangean decomposition. We show empirically that our method outperforms state-of-the-art Lagrangean decomposition based algorithms on some challenging Markov Random Field, multi-label discrete tomography and graph matching problems.

Distillation-based training for multi-exit architectures - Bui Thi Mai, Phuong; Lampert, Christoph (IEEE International Conference on Computer Vision)
Multi-exit architectures, in which a stack of processing layers is interleaved with early output layers, allow the processing of a test example to stop early and thus save computation time and/or energy. In this work, we propose a new training procedure for multi-exit architectures based on the principle of knowledge distillation. The method encourage searly exits to mimic later, more accurate exits, by matching their output probabilities. Experiments on CIFAR100 and ImageNet show that distillation-based training significantly improves the accuracy of early exits while maintaining state-of-the-art accuracy for late ones. The method is particularly beneficial when training data is limited and it allows a straightforward extension to semi-supervised learning,i.e. making use of unlabeled data at training time. Moreover, it takes only afew lines to implement and incurs almost no computational overhead at training time, and none at all at test time.

Powerset convolutional neural networks - Wendler, Chris; Alistarh, Dan-Adrian; Püschel, Markus
We present a novel class of convolutional neural networks (CNNs) for set functions,i.e., data indexed with the powerset of a finite set. The convolutions are derivedas linear, shift-equivariant functions for various notions of shifts on set functions.The framework is fundamentally different from graph convolutions based on theLaplacian, as it provides not one but several basic shifts, one for each element inthe ground set. Prototypical experiments with several set function classificationtasks on synthetic datasets and on datasets derived from real-world hypergraphsdemonstrate the potential of our new powerset CNNs.

Detecting visual relationships using box attention - Kolesnikov, Alexander; Kuznetsova, Alina; Lampert, Christoph; Ferrari, Vittorio (Proceedings of the 2019 International Conference on Computer Vision Workshop)
We propose a new model for detecting visual relationships, such as "person riding motorcycle" or "bottle on table". This task is an important step towards comprehensive structured mage understanding, going beyond detecting individual objects. Our main novelty is a Box Attention mechanism that allows to model pairwise interactions between objects using standard object detection pipelines. The resulting model is conceptually clean, expressive and relies on well-justified training and prediction procedures. Moreover, unlike previously proposed approaches, our model does not introduce any additional complex components or hyperparameters on top of those already required by the underlying detection model. We conduct an experimental evaluation on two datasets, V-COCO and Open Images, demonstrating strong quantitative and qualitative results.

Stronger counterexamples to the topological Tverberg conjecture - Avvakumov, Sergey; Karasev, R.; Skopenkov, A. (arXiv)
Denote by ∆N the N-dimensional simplex. A map f : ∆N → Rd is an almost r-embedding if fσ1∩. . .∩fσr = ∅ whenever σ1, . . . , σr are pairwise disjoint faces. A counterexample to the topological Tverberg conjecture asserts that if r is not a prime power and d ≥ 2r + 1, then there is an almost r-embedding ∆(d+1)(r−1) → Rd. This was improved by Blagojevi´c–Frick–Ziegler using a simple construction of higher-dimensional counterexamples by taking k-fold join power of lower-dimensional ones. We improve this further (for d large compared to r): If r is not a prime power and N := (d+ 1)r−r l d + 2 r + 1 m−2, then there is an almost r-embedding ∆N → Rd. For the r-fold van Kampen–Flores conjecture we also produce counterexamples which are stronger than previously known. Our proof is based on generalizations of the Mabillard–Wagner theorem on construction of almost r-embeddings from equivariant maps, and of the Ozaydin theorem on existence of equivariant maps.

Adaptively secure proxy re-encryption - Fuchsbauer, Georg; Kamath Hosdurg, Chethan; Klein, Karen; Pietrzak, Krzysztof Z
A proxy re-encryption (PRE) scheme is a public-key encryption scheme that allows the holder of a key pk to derive a re-encryption key for any other key 𝑝𝑘′. This re-encryption key lets anyone transform ciphertexts under pk into ciphertexts under 𝑝𝑘′ without having to know the underlying message, while transformations from 𝑝𝑘′ to pk should not be possible (unidirectional). Security is defined in a multi-user setting against an adversary that gets the users’ public keys and can ask for re-encryption keys and can corrupt users by requesting their secret keys. Any ciphertext that the adversary cannot trivially decrypt given the obtained secret and re-encryption keys should be secure. All existing security proofs for PRE only show selective security, where the adversary must first declare the users it wants to corrupt. This can be lifted to more meaningful adaptive security by guessing the set of corrupted users among the n users, which loses a factor exponential in Open image in new window , rendering the result meaningless already for moderate Open image in new window . Jafargholi et al. (CRYPTO’17) proposed a framework that in some cases allows to give adaptive security proofs for schemes which were previously only known to be selectively secure, while avoiding the exponential loss that results from guessing the adaptive choices made by an adversary. We apply their framework to PREs that satisfy some natural additional properties. Concretely, we give a more fine-grained reduction for several unidirectional PREs, proving adaptive security at a much smaller loss. The loss depends on the graph of users whose edges represent the re-encryption keys queried by the adversary. For trees and chains the loss is quasi-polynomial in the size and for general graphs it is exponential in their depth and indegree (instead of their size as for previous reductions). Fortunately, trees and low-depth graphs cover many, if not most, interesting applications. Our results apply e.g. to the bilinear-map based PRE schemes by Ateniese et al. (NDSS’05 and CT-RSA’09), Gentry’s FHE-based scheme (STOC’09) and the LWE-based scheme by Chandran et al. (PKC’14).

Stokes flow analogous to viscous electron current in graphene - Mayzel, Jonathan; Steinberg, Victor; Varshney, Atul (Nature Communications)
Electron transport in two-dimensional conducting materials such as graphene, with dominant electron–electron interaction, exhibits unusual vortex flow that leads to a nonlocal current-field relation (negative resistance), distinct from the classical Ohm’s law. The transport behavior of these materials is best described by low Reynolds number hydrodynamics, where the constitutive pressure–speed relation is Stoke’s law. Here we report evidence of such vortices observed in a viscous flow of Newtonian fluid in a microfluidic device consisting of a rectangular cavity—analogous to the electronic system. We extend our experimental observations to elliptic cavities of different eccentricities, and validate them by numerically solving bi-harmonic equation obtained for the viscous flow with no-slip boundary conditions. We verify the existence of a predicted threshold at which vortices appear. Strikingly, we find that a two-dimensional theoretical model captures the essential features of three-dimensional Stokes flow in experiments.

Elastic alfven waves in elastic turbulence - Varshney, Atul; Steinberg, Victor (Nature Communications)
Speed of sound waves in gases and liquids are governed by the compressibility of the medium. There exists another type of non-dispersive wave where the wave speed depends on stress instead of elasticity of the medium. A well-known example is the Alfven wave, which propagates through plasma permeated by a magnetic field with the speed determined by magnetic tension. An elastic analogue of Alfven waves has been predicted in a flow of dilute polymer solution where the elastic stress of the stretching polymers determines the elastic wave speed. Here we present quantitative evidence of elastic Alfven waves in elastic turbulence of a viscoelastic creeping flow between two obstacles in channel flow. The key finding in the experimental proof is a nonlinear dependence of the elastic wave speed cel on the Weissenberg number Wi, which deviates from predictions based on a model of linear polymer elasticity.

EGFR controls hair shaft differentiation in a p53-independent manner - Amberg, Nicole; Sotiropoulou, Panagiota A.; Heller, Gerwin; Lichtenberger, Beate M.; Holcmann, Martin; Camurdanoglu, Bahar; Baykuscheva-Gentscheva, Temenuschka; Blanpain, Cedric; Sibilia, Maria (iScience)
Epidermal growth factor receptor (EGFR) signaling controls skin development and homeostasis inmice and humans, and its deficiency causes severe skin inflammation, which might affect epidermalstem cell behavior. Here, we describe the inflammation-independent effects of EGFR deficiency dur-ing skin morphogenesis and in adult hair follicle stem cells. Expression and alternative splicing analysisof RNA sequencing data from interfollicular epidermis and outer root sheath indicate that EGFR con-trols genes involved in epidermal differentiation and also in centrosome function, DNA damage, cellcycle, and apoptosis. Genetic experiments employingp53deletion in EGFR-deficient epidermis revealthat EGFR signaling exhibitsp53-dependent functions in proliferative epidermal compartments, aswell asp53-independent functions in differentiated hair shaft keratinocytes. Loss of EGFR leads toabsence of LEF1 protein specifically in the innermost epithelial hair layers, resulting in disorganizationof medulla cells. Thus, our results uncover important spatial and temporal features of cell-autonomousEGFR functions in the epidermis.

Perturbations of continuum random Schrödinger operators with applications to Anderson orthogonality and the spectral shift function - Dietlein, Adrian M; Gebert, Martin; Müller, Peter (Journal of Spectral Theory)
We study effects of a bounded and compactly supported perturbation on multidimensional continuum random Schrödinger operators in the region of complete localisation. Our main emphasis is on Anderson orthogonality for random Schrödinger operators. Among others, we prove that Anderson orthogonality does occur for Fermi energies in the region of complete localisation with a non-zero probability. This partially confirms recent non-rigorous findings [V. Khemani et al., Nature Phys. 11 (2015), 560–565]. The spectral shift function plays an important role in our analysis of Anderson orthogonality. We identify it with the index of the corresponding pair of spectral projections and explore the consequences thereof. All our results rely on the main technical estimate of this paper which guarantees separate exponential decay of the disorder-averaged Schatten p-norm of χa(f(H)−f(Hτ))χb in a and b. Here, Hτ is a perturbation of the random Schrödinger operator H, χa is the multiplication operator corresponding to the indicator function of a unit cube centred about a∈Rd, and f is in a suitable class of functions of bounded variation with distributional derivative supported in the region of complete localisation for H.
Keywords: Random Schrödinger operators; spectral shift function; Anderson orthogonality

A mean-field model with discontinuous coefficients for neurons with spatial interaction - Flandoli, Franco; Priola, Enrico; Zanco, Giovanni A (Discrete and Continuous Dynamical Systems)
Starting from a microscopic model for a system of neurons evolving in time which individually follow a stochastic integrate-and-fire type model, we study a mean-field limit of the system. Our model is described by a system of SDEs with discontinuous coefficients for the action potential of each neuron and takes into account the (random) spatial configuration of neurons allowing the interaction to depend on it. In the limit as the number of particles tends to infinity, we obtain a nonlinear Fokker-Planck type PDE in two variables, with derivatives only with respect to one variable and discontinuous coefficients. We also study strong well-posedness of the system of SDEs and prove the existence and uniqueness of a weak measure-valued solution to the PDE, obtained as the limit of the laws of the empirical measures for the system of particles.
Keywords: Applied Mathematics; Discrete Mathematics and Combinatorics; Analysis

Does preprocessing help under congestion? - Foerster, Klaus-Tycho; Korhonen, Janne; Rybicki, Joel; Schmid, Stefan (Proceedings of the 2019 ACM Symposium on Principles of Distributed Computing)
This paper investigates the power of preprocessing in the CONGEST model. Schmid and Suomela (ACM HotSDN 2013) introduced the SUPPORTED CONGEST model to study the application of distributed algorithms in Software-Defined Networks (SDNs). In this paper, we show that a large class of lower bounds in the CONGEST model still hold in the SUPPORTED model, highlighting the robustness of these bounds. This also raises the question how much does preprocessing help in the CONGEST model.

Autoregulation of bacterial gene expression: lessons from the MazEF toxin–antitoxin system - Nikolic, Nela (Current Genetics)
Autoregulation is the direct modulation of gene expression by the product of the corresponding gene. Autoregulation of bacterial gene expression has been mostly studied at the transcriptional level, when a protein acts as the cognate transcriptional repressor. A recent study investigating dynamics of the bacterial toxin–antitoxin MazEF system has shown how autoregulation at both the transcriptional and post-transcriptional levels affects the heterogeneity of Escherichia coli populations. Toxin–antitoxin systems hold a crucial but still elusive part in bacterial response to stress. This perspective highlights how these modules can also serve as a great model system for investigating basic concepts in gene regulation. However, as the genomic background and environmental conditions substantially influence toxin activation, it is important to study (auto)regulation of toxin–antitoxin systems in well-defined setups as well as in conditions that resemble the environmental niche.

Bi-Sobolev solutions to the prescribed Jacobian inequality in the plane with L p data and applications to nonlinear elasticity - Fischer, Julian L; Kneuss, Olivier (Journal of Differential Equations)
We construct planar bi-Sobolev mappings whose local volume distortion is bounded from below by a given function f∈Lp with p>1. More precisely, for any 1<q<(p+1)/2 we construct W1,q-bi-Sobolev maps with identity boundary conditions; for f∈L∞, we provide bi-Lipschitz maps. The basic building block of our construction are bi-Lipschitz maps which stretch a given compact subset of the unit square by a given factor while preserving the boundary. The construction of these stretching maps relies on a slight strengthening of the celebrated covering result of Alberti, Csörnyei, and Preiss for measurable planar sets in the case of compact sets. We apply our result to a model functional in nonlinear elasticity, the integrand of which features fast blowup as the Jacobian determinant of the deformation becomes small. For such functionals, the derivation of the equilibrium equations for minimizers requires an additional regularization of test functions, which our maps provide.

Epigenetic cues modulating the generation of cell type diversity in the cerebral cortex - Amberg, Nicole; Laukoter, Susanne; Hippenmeyer, Simon (Journal of Neurochemistry)
The cerebral cortex is composed of a large variety of distinct cell-types including projection neurons, interneurons and glial cells which emerge from distinct neural stem cell (NSC) lineages. The vast majority of cortical projection neurons and certain classes of glial cells are generated by radial glial progenitor cells (RGPs) in a highly orchestrated manner. Recent studies employing single cell analysis and clonal lineage tracing suggest that NSC and RGP lineage progression are regulated in a profound deterministic manner. In this review we focus on recent advances based mainly on correlative phenotypic data emerging from functional genetic studies in mice. We establish hypotheses to test in future research and outline a conceptual framework how epigenetic cues modulate the generation of cell-type diversity during cortical development. This article is protected by copyright. All rights reserved.

Fluidization-mediated tissue spreading by mitotic cell rounding and non-canonical Wnt signalling - Petridou, Nicoletta; Grigolon, Silvia; Salbreux, Guillaume; Hannezo, Edouard B; Heisenberg, Carl-Philipp J (Nature Cell Biology)
Tissue morphogenesis is driven by mechanical forces that elicit changes in cell size, shape and motion. The extent by which forces deform tissues critically depends on the rheological properties of the recipient tissue. Yet, whether and how dynamic changes in tissue rheology affect tissue morphogenesis and how they are regulated within the developing organism remain unclear. Here, we show that blastoderm spreading at the onset of zebrafish morphogenesis relies on a rapid, pronounced and spatially patterned tissue fluidization. Blastoderm fluidization is temporally controlled by mitotic cell rounding-dependent cell–cell contact disassembly during the last rounds of cell cleavages. Moreover, fluidization is spatially restricted to the central blastoderm by local activation of non-canonical Wnt signalling within the blastoderm margin, increasing cell cohesion and thereby counteracting the effect of mitotic rounding on contact disassembly. Overall, our results identify a fluidity transition mediated by loss of cell cohesion as a critical regulator of embryo morphogenesis.

Harmonic dynamics of the Abelian sandpile - Lang, Moritz; Shkolnikov, Mikhail (Proceedings of the National Academy of Sciences)
The abelian sandpile serves as a model to study self-organized criticality, a phenomenon occurring in biological, physical and social processes. The identity of the abelian group is a fractal composed of self-similar patches, and its limit is subject of extensive collaborative research. Here, we analyze the evolution of the sandpile identity under harmonic fields of different orders. We show that this evolution corresponds to periodic cycles through the abelian group characterized by the smooth transformation and apparent conservation of the patches constituting the identity. The dynamics induced by second and third order harmonics resemble smooth stretchings, respectively translations, of the identity, while the ones induced by fourth order harmonics resemble magnifications and rotations. Starting with order three, the dynamics pass through extended regions of seemingly random configurations which spontaneously reassemble into accentuated patterns. We show that the space of harmonic functions projects to the extended analogue of the sandpile group, thus providing a set of universal coordinates identifying configurations between different domains. Since the original sandpile group is a subgroup of the extended one, this directly implies that it admits a natural renormalization. Furthermore, we show that the harmonic fields can be induced by simple Markov processes, and that the corresponding stochastic dynamics show remarkable robustness over hundreds of periods. Finally, we encode information into seemingly random configurations, and decode this information with an algorithm requiring minimal prior knowledge. Our results suggest that harmonic fields might split the sandpile group into sub-sets showing different critical coefficients, and that it might be possible to extend the fractal structure of the identity beyond the boundaries of its domain.

Disentangling factors of variation using few labels - Locatello, Francesco; Tschannen, Michael; Bauer, Stefan; Rätsch, Gunnar; Schölkopf, Bernhard; Bachem, Olivier (8th International Conference on Learning Representations)
Learning disentangled representations is considered a cornerstone problem in representation learning. Recently, Locatello et al. (2019) demonstrated that unsupervised disentanglement learning without inductive biases is theoretically impossible and that existing inductive biases and unsupervised methods do not allow to consistently learn disentangled representations. However, in many practical settings, one might have access to a limited amount of supervision, for example through manual labeling of (some) factors of variation in a few training examples. In this paper, we investigate the impact of such supervision on state-of-the-art disentanglement methods and perform a large scale study, training over 52000 models under well-defined and reproducible experimental conditions. We observe that a small number of labeled examples (0.01--0.5% of the data set), with potentially imprecise and incomplete labels, is sufficient to perform model selection on state-of-the-art unsupervised models. Further, we investigate the benefit of incorporating supervision into the training process. Overall, we empirically validate that with little and imprecise supervision it is possible to reliably learn disentangled representations.

The incomplete Rosetta Stone problem: Identifiability results for multi-view nonlinear ICA - Gresele, Luigi; Rubenstein, Paul K.; Mehrjou, Arash; Locatello, Francesco; Schölkopf, Bernhard (Proceedings of the 35th Conference on Uncertainty in Artificial Intelligence)
We consider the problem of recovering a common latent source with independent components from multiple views. This applies to settings in which a variable is measured with multiple experimental modalities, and where the goal is to synthesize the disparate measurements into a single unified representation. We consider the case that the observed views are a nonlinear mixing of component-wise corruptions of the sources. When the views are considered separately, this reduces to nonlinear Independent Component Analysis (ICA) for which it is provably impossible to undo the mixing. We present novel identifiability proofs that this is possible when the multiple views are considered jointly, showing that the mixing can theoretically be undone using function approximators such as deep neural networks. In contrast to known identifiability results for nonlinear ICA, we prove that independent latent sources with arbitrary mixing can be recovered as long as multiple, sufficiently different noisy views are available.

On the fairness of disentangled representations - Locatello, Francesco; Abbati, Gabriele; Rainforth, Tom; Bauer, Stefan; Schölkopf, Bernhard; Bachem, Olivier (Advances in Neural Information Processing Systems)
Recently there has been a significant interest in learning disentangled representations, as they promise increased interpretability, generalization to unseen scenarios and faster learning on downstream tasks. In this paper, we investigate the usefulness of different notions of disentanglement for improving the fairness of downstream prediction tasks based on representations. We consider the setting where the goal is to predict a target variable based on the learned representation of high-dimensional observations (such as images) that depend on both the target variable and an unobserved sensitive variable. We show that in this setting both the optimal and empirical predictions can be unfair, even if the target variable and the sensitive variable are independent. Analyzing the representations of more than \num{12600} trained state-of-the-art disentangled models, we observe that several disentanglement scores are consistently correlated with increased fairness, suggesting that disentanglement may be a useful property to encourage fairness when sensitive variables are not observed.

Stochastic Frank-Wolfe for composite convex minimization - Locatello, Francesco; Yurtsever, Alp; Fercoq, Olivier; Cevher, Volkan (Advances in Neural Information Processing Systems)
A broad class of convex optimization problems can be formulated as a semidefinite program (SDP), minimization of a convex function over the positive-semidefinite cone subject to some affine constraints. The majority of classical SDP solvers are designed for the deterministic setting where problem data is readily available. In this setting, generalized conditional gradient methods (aka Frank-Wolfe-type methods) provide scalable solutions by leveraging the so-called linear minimization oracle instead of the projection onto the semidefinite cone. Most problems in machine learning and modern engineering applications, however, contain some degree of stochasticity. In this work, we propose the first conditional-gradient-type method for solving stochastic optimization problems under affine constraints. Our method guarantees O(k−1/3) convergence rate in expectation on the objective residual and O(k−5/12) on the feasibility gap.

Are disentangled representations helpful for abstract visual reasoning? - Steenkiste, Sjoerd van; Locatello, Francesco; Schmidhuber, Jürgen; Bachem, Olivier (Advances in Neural Information Processing Systems)
A disentangled representation encodes information about the salient factors of variation in the data independently. Although it is often argued that this representational format is useful in learning to solve many real-world down-stream tasks, there is little empirical evidence that supports this claim. In this paper, we conduct a large-scale study that investigates whether disentangled representations are more suitable for abstract reasoning tasks. Using two new tasks similar to Raven's Progressive Matrices, we evaluate the usefulness of the representations learned by 360 state-of-the-art unsupervised disentanglement models. Based on these representations, we train 3600 abstract reasoning models and observe that disentangled representations do in fact lead to better down-stream performance. In particular, they enable quicker learning using fewer samples.

Challenging common assumptions in the unsupervised learning of disentangled representations - Locatello, Francesco; Bauer, Stefan; Lucic, Mario; Rätsch, Gunnar; Gelly, Sylvain; Schölkopf, Bernhard; Bachem, Olivier (Proceedings of the 36th International Conference on Machine Learning)
The key idea behind the unsupervised learning of disentangled representations is that real-world data is generated by a few explanatory factors of variation which can be recovered by unsupervised learning algorithms. In this paper, we provide a sober look at recent progress in the field and challenge some common assumptions. We first theoretically show that the unsupervised learning of disentangled representations is fundamentally impossible without inductive biases on both the models and the data. Then, we train more than 12000 models covering most prominent methods and evaluation metrics in a reproducible large-scale experimental study on seven different data sets. We observe that while the different methods successfully enforce properties ``encouraged'' by the corresponding losses, well-disentangled models seemingly cannot be identified without supervision. Furthermore, increased disentanglement does not seem to lead to a decreased sample complexity of learning for downstream tasks. Our results suggest that future work on disentanglement learning should be explicit about the role of inductive biases and (implicit) supervision, investigate concrete benefits of enforcing disentanglement of the learned representations, and consider a reproducible experimental setup covering several data sets.

Limiting shapes of confined lipid vesicles - Kavcic, Bor; Sakashita, A.; Noguchi, H.; Ziherl, P. (Soft Matter)
We theoretically study the shapes of lipid vesicles confined to a spherical cavity, elaborating a framework based on the so-called limiting shapes constructed from geometrically simple structural elements such as double-membrane walls and edges. Partly inspired by numerical results, the proposed non-compartmentalized and compartmentalized limiting shapes are arranged in the bilayer-couple phase diagram which is then compared to its free-vesicle counterpart. We also compute the area-difference-elasticity phase diagram of the limiting shapes and we use it to interpret shape transitions experimentally observed in vesicles confined within another vesicle. The limiting-shape framework may be generalized to theoretically investigate the structure of certain cell organelles such as the mitochondrion.

On the geometry of geodesics in discrete optimal transport - Erbar, Matthias; Maas, Jan; Wirth, Melchior (Calculus of Variations and Partial Differential Equations)
We consider the space of probability measures on a discrete set X, endowed with a dynamical optimal transport metric. Given two probability measures supported in a subset Y⊆X, it is natural to ask whether they can be connected by a constant speed geodesic with support in Y at all times. Our main result answers this question affirmatively, under a suitable geometric condition on Y introduced in this paper. The proof relies on an extension result for subsolutions to discrete Hamilton-Jacobi equations, which is of independent interest.

On the transfer of inductive bias from simulation to the real world: a new disentanglement dataset - Gondal, Muhammad Waleed; Wüthrich, Manuel; Miladinović, Đorđe; Locatello, Francesco; Breidt, Martin; Volchkov, Valentin; Akpo, Joel; Bachem, Olivier; Schölkopf, Bernhard; Bauer, Stefan (Advances in Neural Information Processing Systems)
Learning meaningful and compact representations with disentangled semantic aspects is considered to be of key importance in representation learning. Since real-world data is notoriously costly to collect, many recent state-of-the-art disentanglement models have heavily relied on synthetic toy data-sets. In this paper, we propose a novel data-set which consists of over one million images of physical 3D objects with seven factors of variation, such as object color, shape, size and position. In order to be able to control all the factors of variation precisely, we built an experimental platform where the objects are being moved by a robotic arm. In addition, we provide two more datasets which consist of simulations of the experimental setup. These datasets provide for the first time the possibility to systematically investigate how well different disentanglement methods perform on real data in comparison to simulation, and how simulated data can be leveraged to build better representations of the real world. We provide a first experimental study of these questions and our results indicate that learned models transfer poorly, but that model and hyperparameter selection is an effective means of transferring information to the real world.

Recognizing weak embeddings of graphs - Akitaya, Hugo; Fulek, Radoslav; Tóth, Csaba (ACM Transactions on Algorithms)
We present an efficient algorithm for a problem in the interface between clustering and graph embeddings. An embedding ϕ : G → M of a graph G into a 2-manifold M maps the vertices in V(G) to distinct points and the edges in E(G) to interior-disjoint Jordan arcs between the corresponding vertices. In applications in clustering, cartography, and visualization, nearby vertices and edges are often bundled to the same point or overlapping arcs due to data compression or low resolution. This raises the computational problem of deciding whether a given map ϕ : G → M comes from an embedding. A map ϕ : G → M is a weak embedding if it can be perturbed into an embedding ψ ϵ : G → M with ‖ ϕ − ψ ϵ ‖ < ϵ for every ϵ > 0, where ‖.‖ is the unform norm. A polynomial-time algorithm for recognizing weak embeddings has recently been found by Fulek and Kynčl. It reduces the problem to solving a system of linear equations over Z2. It runs in O(n2ω)≤ O(n4.75) time, where ω ∈ [2,2.373) is the matrix multiplication exponent and n is the number of vertices and edges of G. We improve the running time to O(n log n). Our algorithm is also conceptually simpler: We perform a sequence of local operations that gradually “untangles” the image ϕ(G) into an embedding ψ(G) or reports that ϕ is not a weak embedding. It combines local constraints on the orientation of subgraphs directly, thereby eliminating the need for solving large systems of linear equations.

Automatic time-unbounded reachability analysis of hybrid systems - Giacobbe, Mirco
Hybrid automata combine finite automata and dynamical systems, and model the interaction of digital with physical systems. Formal analysis that can guarantee the safety of all behaviors or rigorously witness failures, while unsolvable in general, has been tackled algorithmically using, e.g., abstraction, bounded model-checking, assisted theorem proving. Nevertheless, very few methods have addressed the time-unbounded reachability analysis of hybrid automata and, for current sound and automatic tools, scalability remains critical. We develop methods for the polyhedral abstraction of hybrid automata, which construct coarse overapproximations and tightens them incrementally, in a CEGAR fashion. We use template polyhedra, i.e., polyhedra whose facets are normal to a given set of directions. While, previously, directions were given by the user, we introduce (1) the first method for computing template directions from spurious counterexamples, so as to generalize and eliminate them. The method applies naturally to convex hybrid automata, i.e., hybrid automata with (possibly non-linear) convex constraints on derivatives only, while for linear ODE requires further abstraction. Specifically, we introduce (2) the conic abstractions, which, partitioning the state space into appropriate (possibly non-uniform) cones, divide curvy trajectories into relatively straight sections, suitable for polyhedral abstractions. Finally, we introduce (3) space-time interpolation, which, combining interval arithmetic and template refinement, computes appropriate (possibly non-uniform) time partitioning and template directions along spurious trajectories, so as to eliminate them. We obtain sound and automatic methods for the reachability analysis over dense and unbounded time of convex hybrid automata and hybrid automata with linear ODE. We build prototype tools and compare—favorably—our methods against the respective state-of-the-art tools, on several benchmarks.

Data from: The consequences of an introgression event - Barton, Nicholas H
The spread of adaptive alleles is fundamental to evolution, and in theory, this process is well‐understood. However, only rarely can we follow this process—whether it originates from the spread of a new mutation, or by introgression from another population. In this issue of Molecular Ecology, Hanemaaijer et al. (2018) report on a 25‐year long study of the mosquitoes Anopheles gambiae (Figure 1) and Anopheles coluzzi in Mali, based on genotypes at 15 single‐nucleotide polymorphism (SNP). The species are usually reproductively isolated from each other, but in 2002 and 2006, bursts of hybridization were observed, when F1 hybrids became abundant. Alleles backcrossed from A. gambiae into A. coluzzi, but after the first event, these declined over the following years. In contrast, after 2006, an insecticide resistance allele that had established in A. gambiae spread into A. coluzzi, and rose to high frequency there, over 6 years (~75 generations). Whole genome sequences of 74 individuals showed that A. gambiae SNP from across the genome had become common in the A. coluzzi population, but that most of these were clustered in 34 genes around the resistance locus. A new set of SNP from 25 of these genes were assayed over time; over the 4 years since near‐fixation of the resistance allele; some remained common, whereas others declined. What do these patterns tell us about this introgression event?

The Repo homeodomain transcription factor suppresses hematopoiesis in Drosophila and preserves the glial fate - Trébuchet, Guillaume; Cattenoz, Pierre B; Zsámboki, János; Mazaud, David; Siekhaus, Daria E; Fanto, Manolis; Giangrande, Angela (Journal of Neuroscience)
Despite their different origins, Drosophila glia and hemocytes are related cell populations that provide an immune function. Drosophila hemocytes patrol the body cavity and act as macrophages outside the nervous system whereas glia originate from the neuroepithelium and provide the scavenger population of the nervous system. Drosophila glia are hence the functional orthologs of vertebrate microglia, even though the latter are cells of immune origin that subsequently move into the brain during development. Interestingly, the Drosophila immune cells within (glia) and outside the nervous system (hemocytes) require the same transcription factor Glide/Gcm for their development. This raises the issue of how do glia specifically differentiate in the nervous system and hemocytes in the procephalic mesoderm. The Repo homeodomain transcription factor and pan-glial direct target of Glide/Gcm is known to ensure glial terminal differentiation. Here we show that Repo also takes center stage in the process that discriminates between glia and hemocytes. First, Repo expression is repressed in the hemocyte anlagen by mesoderm-specific factors. Second, Repo ectopic activation in the procephalic mesoderm is sufficient to repress the expression of hemocyte-specific genes. Third, the lack of Repo triggers the expression of hemocyte markers in glia. Thus, a complex network of tissue-specific cues biases the potential of Glide/Gcm. These data allow us to revise the concept of fate determinants and help us understand the bases of cell specification. Both sexes were analyzed.SIGNIFICANCE STATEMENTDistinct cell types often require the same pioneer transcription factor, raising the issue of how does one factor trigger different fates. In Drosophila, glia and hemocytes provide a scavenger activity within and outside the nervous system, respectively. While they both require the Glide/Gcm transcription factor, glia originate from the ectoderm, hemocytes from the mesoderm. Here we show that tissue-specific factors inhibit the gliogenic potential of Glide/Gcm in the mesoderm by repressing the expression of the homeodomain protein Repo, a major glial-specific target of Glide/Gcm. Repo expression in turn inhibits the expression of hemocyte-specific genes in the nervous system. These cell-specific networks secure the establishment of the glial fate only in the nervous system and allow cell diversification.

The wonderful compactification for quantum groups - Ganev, Iordan V (Journal of the London Mathematical Society)
In this paper, we introduce a quantum version of the wonderful compactification of a group as a certain noncommutative projective scheme. Our approach stems from the fact that the wonderful compactification encodes the asymptotics of matrix coefficients, and from its realization as a GIT quotient of the Vinberg semigroup. In order to define the wonderful compactification for a quantum group, we adopt a generalized formalism of Proj categories in the spirit of Artin and Zhang. Key to our construction is a quantum version of the Vinberg semigroup, which we define as a q-deformation of a certain Rees algebra, compatible with a standard Poisson structure. Furthermore, we discuss quantum analogues of the stratification of the wonderful compactification by orbits for a certain group action, and provide explicit computations in the case of SL2.

Molecular mechanisms of endomembrane trafficking in Arabidopsis thaliana - Vasileva, Mina K
The development and growth of Arabidopsis thaliana is regulated by a combination of genetic programing and also by the environmental influences. An important role in these processes play the phytohormones and among them, auxin is crucial as it controls many important functions. It is transported through the whole plant body by creating local and temporal concentration maxima and minima, which have an impact on the cell status, tissue and organ identity. Auxin has the property to undergo a directional and finely regulated cell-to-cell transport, which is enabled by the transport proteins, localized on the plasma membrane. An important role in this process have the PIN auxin efflux proteins, which have an asymmetric/polar subcellular localization and determine the directionality of the auxin transport. During the last years, there were significant advances in understanding how the trafficking molecular machineries function, including studies on molecular interactions, function, subcellular localization and intracellular distribution. However, there is still a lack of detailed characterization on the steps of endocytosis, exocytosis, endocytic recycling and degradation. Due to this fact, I focused on the identification of novel trafficking factors and better characterization of the intracellular trafficking pathways. My PhD thesis consists of an introductory chapter, three experimental chapters, a chapter containing general discussion, conclusions and perspectives and also an appendix chapter with published collaborative papers. The first chapter is separated in two different parts: I start by a general introduction to auxin biology and then I introduce the trafficking pathways in the model plant Arabidopsis thaliana. Then, I explain also the phosphorylation-signals for polar targeting and also the roles of the phytohormone strigolactone. The second chapter includes the characterization of bar1/sacsin mutant, which was identified in a forward genetic screen for novel trafficking components in Arabidopsis thaliana, where by the implementation of an EMS-treated pPIN1::PIN1-GFP marker line and by using the established inhibitor of ARF-GEFs, Brefeldin A (BFA) as a tool to study trafficking processes, we identified a novel factor, which is mediating the adaptation of the plant cell to ARF-GEF inhibition. The mutation is in a previously uncharacterized gene, encoding a very big protein that we, based on its homologies, called SACSIN with domains suggesting roles as a molecular chaperon or as a component of the ubiquitin-proteasome system. Our physiology and imaging studies revealed that SACSIN is a crucial plant cell component of the adaptation to the ARF-GEF inhibition. The third chapter includes six subchapters, where I focus on the role of the phytohormone strigolactone, which interferes with auxin feedback on PIN internalization. Strigolactone moderates the polar auxin transport by increasing the internalization of the PIN auxin efflux carriers, which reduces the canalization related growth responses. In addition, I also studied the role of phosphorylation in the strigolactone regulation of auxin feedback on PIN internalization. In this chapter I also present my results on the MAX2-dependence of strigolactone-mediated root growth inhibition and I also share my results on the auxin metabolomics profiling after application of GR24. In the fourth chapter I studied the effect of two small molecules ES-9 and ES9-17, which were identified from a collection of small molecules with the property to impair the clathrin-mediated endocytosis. In the fifth chapter, I discuss all my observations and experimental findings and suggest alternative hypothesis to interpret my results. In the appendix there are three collaborative published projects. In the first, I participated in the characterization of the role of ES9 as a small molecule, which is inhibitor of clathrin- mediated endocytosis in different model organisms. In the second paper, I contributed to the characterization of another small molecule ES9-17, which is a non-protonophoric analog of ES9 and also impairs the clathrin-mediated endocytosis not only in plant cells, but also in mammalian HeLa cells. Last but not least, I also attach another paper, where I tried to establish the grafting method as a technique in our lab to study canalization related processes.

Fluid dynamics during bleb formation in migrating cells in vivo - Goudarzi, Mohammad; Boquet-Pujadas, Aleix; Olivo-Marin, Jean Christophe; Raz, Erez (PLOS ONE)
Blebs are cellular protrusions observed in migrating cells and in cells undergoing spreading, cytokinesis, and apoptosis. Here we investigate the flow of cytoplasm during bleb formation and the concurrent changes in cell volume using zebrafish primordial germ cells (PGCs) as an in vivo model. We show that bleb inflation occurs concomitantly with cytoplasmic inflow into it and that during this process the total cell volume does not change. We thus show that bleb formation in primordial germ cells results primarily from redistribution of material within the cell rather than being driven by flow of water from an external source.

Estimating information flow in single cells - Cepeda Humerez, Sarah A
Single cells are constantly interacting with their environment and each other, more importantly, the accurate perception of environmental cues is crucial for growth, survival, and reproduction. This communication between cells and their environment can be formalized in mathematical terms and be quantified as the information flow between them, as prescribed by information theory. The recent availability of real–time dynamical patterns of signaling molecules in single cells has allowed us to identify encoding about the identity of the environment in the time–series. However, efficient estimation of the information transmitted by these signals has been a data–analysis challenge due to the high dimensionality of the trajectories and the limited number of samples. In the first part of this thesis, we develop and evaluate decoding–based estimation methods to lower bound the mutual information and derive model–based precise information estimates for biological reaction networks governed by the chemical master equation. This is followed by applying the decoding-based methods to study the intracellular representation of extracellular changes in budding yeast, by observing the transient dynamics of nuclear translocation of 10 transcription factors in response to 3 stress conditions. Additionally, we apply these estimators to previously published data on ERK and Ca2+ signaling and yeast stress response. We argue that this single cell decoding-based measure of information provides an unbiased, quantitative and interpretable measure for the fidelity of biological signaling processes. Finally, in the last section, we deal with gene regulation which is primarily controlled by transcription factors (TFs) that bind to the DNA to activate gene expression. The possibility that non-cognate TFs activate transcription diminishes the accuracy of regulation with potentially disastrous effects for the cell. This ’crosstalk’ acts as a previously unexplored source of noise in biochemical networks and puts a strong constraint on their performance. To mitigate erroneous initiation we propose an out of equilibrium scheme that implements kinetic proofreading. We show that such architectures are favored over their equilibrium counterparts for complex organisms despite introducing noise in gene expression.
Keywords: Information estimation; Time-series; data analysis

Coevolution of transcription factors and their binding sites in sequence space - Prizak, Roshan
Transcription factors, by binding to specific sequences on the DNA, control the precise spatio-temporal expression of genes inside a cell. However, this specificity is limited, leading to frequent incorrect binding of transcription factors that might have deleterious consequences on the cell. By constructing a biophysical model of TF-DNA binding in the context of gene regulation, I will first explore how regulatory constraints can strongly shape the distribution of a population in sequence space. Then, by directly linking this to a picture of multiple types of transcription factors performing their functions simultaneously inside the cell, I will explore the extent of regulatory crosstalk -- incorrect binding interactions between transcription factors and binding sites that lead to erroneous regulatory states -- and understand the constraints this places on the design of regulatory systems. I will then develop a generic theoretical framework to investigate the coevolution of multiple transcription factors and multiple binding sites, in the context of a gene regulatory network that performs a certain function. As a particular tractable version of this problem, I will consider the evolution of two transcription factors when they transmit upstream signals to downstream target genes. Specifically, I will describe the evolutionary steady states and the evolutionary pathways involved, along with their timescales, of a system that initially undergoes a transcription factor duplication event. To connect this important theoretical model to the prominent biological event of transcription factor duplication giving rise to paralogous families, I will then describe a bioinformatics analysis of C2H2 Zn-finger transcription factors, a major family in humans, and focus on the patterns of evolution that paralogs have undergone in their various protein domains in the recent past.

On derived equivalences of k3 surfaces in positive characteristic - Srivastava, Tanya K (Documenta Mathematica)
For an ordinary K3 surface over an algebraically closed field of positive characteristic we show that every automorphism lifts to characteristic zero. Moreover, we show that the Fourier-Mukai partners of an ordinary K3 surface are in one-to-one correspondence with the Fourier-Mukai partners of the geometric generic fiber of its canonical lift. We also prove that the explicit counting formula for Fourier-Mukai partners of the K3 surfaces with Picard rank two and with discriminant equal to minus of a prime number, in terms of the class number of the prime, holds over a field of positive characteristic as well. We show that the image of the derived autoequivalence group of a K3 surface of finite height in the group of isometries of its crystalline cohomology has index at least two. Moreover, we provide a conditional upper bound on the kernel of this natural cohomological descent map. Further, we give an extended remark in the appendix on the possibility of an F-crystal structure on the crystalline cohomology of a K3 surface over an algebraically closed field of positive characteristic and show that the naive F-crystal structure fails in being compatible with inner product.

Limit law of a second class particle in TASEP with non-random initial condition - Ferrari, Patrick; Ghosal, Promit; Nejjar, Peter (Annales de l'institut Henri Poincare (B) Probability and Statistics)
We consider the totally asymmetric simple exclusion process (TASEP) with non-random initial condition having density ρ on ℤ− and λ on ℤ+, and a second class particle initially at the origin. For ρ<λ, there is a shock and the second class particle moves with speed 1−λ−ρ. For large time t, we show that the position of the second class particle fluctuates on a t1/3 scale and determine its limiting law. We also obtain the limiting distribution of the number of steps made by the second class particle until time t.

An Austrian proposal for the classification of Open Access Tuples (COAT) - distinguish different open access types beyond colors - Danowski, Patrick (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare)
In this article a model is described how Open Access definitions can be formed on the basis of objective criteria. The common Open Access definitions such as "gold" and "green" are not exactly defined. This becomes a problem as soon as one begins to measure Open Access, for example if the development of the Open Access share should be monitored. This was discussed in the working group on Open Access Monitoring of the AT2OA project and the present model was developed, which is based on 5 critics with 4 characteristics: location, licence, version, embargo and conditions of the Open Access publication are taken into account. In the meantime, the model has also been tested in practice using R scripts, and the initial results are quite promising.

Location of the spectrum of Kronecker random matrices - Alt, Johannes; Erdös, László; Krüger, Torben H; Nemish, Yuriy (Annales de l'institut Henri Poincare)
For a general class of large non-Hermitian random block matrices X we prove that there are no eigenvalues away from a deterministic set with very high probability. This set is obtained from the Dyson equation of the Hermitization of X as the self-consistent approximation of the pseudospectrum. We demonstrate that the analysis of the matrix Dyson equation from (Probab. Theory Related Fields (2018)) offers a unified treatment of many structured matrix ensembles.

The Airn lncRNA does not require any DNA elements within its locus to silence distant imprinted genes - Andergassen, Daniel; Muckenhuber, Markus; Bammer, Philipp C.; Kulinski, Tomasz M.; Theussl, Hans-Christian; Shimizu, Takahiko; Penninger, Josef M.; Pauler, Florian; Hudson, Quanah J. (PLoS Genetics)
Long non-coding (lnc) RNAs are numerous and found throughout the mammalian genome, and many are thought to be involved in the regulation of gene expression. However, the majority remain relatively uncharacterised and of uncertain function making the use of model systems to uncover their mode of action valuable. Imprinted lncRNAs target and recruit epigenetic silencing factors to a cluster of imprinted genes on the same chromosome, making them one of the best characterized lncRNAs for silencing distant genes in cis. In this study we examined silencing of the distant imprinted gene Slc22a3 by the lncRNA Airn in the Igf2r imprinted cluster in mouse. Previously we proposed that imprinted lncRNAs may silence distant imprinted genes by disrupting promoter-enhancer interactions by being transcribed through the enhancer, which we called the enhancer interference hypothesis. Here we tested this hypothesis by first using allele-specific chromosome conformation capture (3C) to detect interactions between the Slc22a3 promoter and the locus of the Airn lncRNA that silences it on the paternal chromosome. In agreement with the model, we found interactions enriched on the maternal allele across the entire Airn gene consistent with multiple enhancer-promoter interactions. Therefore, to test the enhancer interference hypothesis we devised an approach to delete the entire Airn gene. However, the deletion showed that there are no essential enhancers for Slc22a2, Pde10a and Slc22a3 within the Airn gene, strongly indicating that the Airn RNA rather than its transcription is responsible for silencing distant imprinted genes. Furthermore, we found that silent imprinted genes were covered with large blocks of H3K27me3 on the repressed paternal allele. Therefore we propose an alternative hypothesis whereby the chromosome interactions may initially guide the lncRNA to target imprinted promoters and recruit repressive chromatin, and that these interactions are lost once silencing is established.

Non-equilibrium critical dynamics of bursts in θ and δ rhythms as fundamental characteristic of sleep and wake micro-architecture - Wang, Jilin W. J. L.; Lombardi, Fabrizio; Zhang, Xiyun; Anaclet, Christelle; Ivanov, Plamen Ch. (PLoS Computational Biology)
Origin and functions of intermittent transitions among sleep stages, including short awakenings and arousals, constitute a challenge to the current homeostatic framework for sleep regulation, focusing on factors modulating sleep over large time scales. Here we propose that the complex micro-architecture characterizing the sleep-wake cycle results from an underlying non-equilibrium critical dynamics, bridging collective behaviors across spatio-temporal scales. We investigate θ and δ wave dynamics in control rats and in rats with lesions of sleep-promoting neurons in the parafacial zone. We demonstrate that intermittent bursts in θ and δ rhythms exhibit a complex temporal organization, with long-range power-law correlations and a robust duality of power law (θ-bursts, active phase) and exponential-like (δ-bursts, quiescent phase) duration distributions, typical features of non-equilibrium systems self-organizing at criticality. Crucially, such temporal organization relates to anti-correlated coupling between θ- and δ-bursts, and is independent of the dominant physiologic state and lesions, a solid indication of a basic principle in sleep dynamics.

Towards understanding knowledge distillation - Bui Thi Mai, Phuong; Lampert, Christoph (Proceedings of the 36th International Conference on Machine Learning)
Knowledge distillation, i.e. one classifier being trained on the outputs of another classifier, is an empirically very successful technique for knowledge transfer between classifiers. It has even been observed that classifiers learn much faster and more reliably if trained with the outputs of another classifier as soft labels, instead of from ground truth data. So far, however, there is no satisfactory theoretical explanation of this phenomenon. In this work, we provide the first insights into the working mechanisms of distillation by studying the special case of linear and deep linear classifiers. Specifically, we prove a generalization bound that establishes fast convergence of the expected risk of a distillation-trained linear classifier. From the bound and its proof we extract three keyfactors that determine the success of distillation: data geometry – geometric properties of the datadistribution, in particular class separation, has an immediate influence on the convergence speed of the risk; optimization bias– gradient descentoptimization finds a very favorable minimum of the distillation objective; and strong monotonicity– the expected risk of the student classifier always decreases when the size of the training set grows.

Robust learning from untrusted sources - Konstantinov, Nikola H; Lampert, Christoph (Proceedings of the 36th International Conference on Machine Learning)
Modern machine learning methods often require more data for training than a single expert can provide. Therefore, it has become a standard procedure to collect data from external sources, e.g. via crowdsourcing. Unfortunately, the quality of these sources is not always guaranteed. As additional complications, the data might be stored in a distributed way, or might even have to remain private. In this work, we address the question of how to learn robustly in such scenarios. Studying the problem through the lens of statistical learning theory, we derive a procedure that allows for learning from all available sources, yet automatically suppresses irrelevant or corrupted data. We show by extensive experiments that our method provides significant improvements over alternative approaches from robust statistics and distributed optimization.

Salicylic acid-mediated plasmodesmal closure via Remorin-dependent lipid organization - Huang, D; Sun, Y; Ma, Z; Ke, M; Cui, Y; Chen, Z; Chen, C; Ji, C; Tran, TM; Yang, L; Lam, SM; Han, Y; et al. (Proceedings of the National Academy of Sciences of the United States of America)
Plasmodesmata (PD) are plant-specific membrane-lined channels that create cytoplasmic and membrane continuities between adjacent cells, thereby facilitating cell–cell communication and virus movement. Plant cells have evolved diverse mechanisms to regulate PD plasticity in response to numerous environmental stimuli. In particular, during defense against plant pathogens, the defense hormone, salicylic acid (SA), plays a crucial role in the regulation of PD permeability in a callose-dependent manner. Here, we uncover a mechanism by which plants restrict the spreading of virus and PD cargoes using SA signaling by increasing lipid order and closure of PD. We showed that exogenous SA application triggered the compartmentalization of lipid raft nanodomains through a modulation of the lipid raft-regulatory protein, Remorin (REM). Genetic studies, superresolution imaging, and transmission electron microscopy observation together demonstrated that Arabidopsis REM1.2 and REM1.3 are crucial for plasma membrane nanodomain assembly to control PD aperture and functionality. In addition, we also found that a 14-3-3 epsilon protein modulates REM clustering and membrane nanodomain compartmentalization through its direct interaction with REM proteins. This study unveils a molecular mechanism by which the key plant defense hormone, SA, triggers membrane lipid nanodomain reorganization, thereby regulating PD closure to impede virus spreading.

On the power to detect rare recombination events - Wright, Alison E.; Darolti, Iulia; Bloch, Natasha I.; Oostra, Vicencio; Sandkam, Benjamin A.; Buechel, Séverine D.; Kolm, Niclas; Breden, Felix; Vicoso, Beatriz; Mank, Judith E. (Proceedings of the National Academy of Sciences of the United States of America)
We read with great interest the recent work in PNAS by Bergero et al. (1) describing differences in male and female recombination patterns on the guppy (Poecilia reticulata) sex chromosome. We fully agree that recombination in males is largely confined to the ends of the sex chromosome. Bergero et al. interpret these results to suggest that our previous findings of population-level variation in the degree of sex chromosome differentiation in this species (2) are incorrect. However, we suggest that their results are entirely consistent with our previous report, and that their interpretation presents a false controversy.

Mating system variation in hybrid zones: Facilitation, barriers and asymmetries to gene flow - Pickup, Melinda; Barton, Nicholas H; Brandvain, Yaniv; Fraisse, Christelle; Yakimowski, Sarah; Dixit, Tanmay; Lexer, Christian; Cereghetti, Eva; Field, David (New Phytologist)
Plant mating systems play a key role in structuring genetic variation both within and between species. In hybrid zones, the outcomes and dynamics of hybridization are usually interpreted as the balance between gene flow and selection against hybrids. Yet, mating systems can introduce selective forces that alter these expectations; with diverse outcomes for the level and direction of gene flow depending on variation in outcrossing and whether the mating systems of the species pair are the same or divergent. We present a survey of hybridization in 133 species pairs from 41 plant families and examine how patterns of hybridization vary with mating system. We examine if hybrid zone mode, level of gene flow, asymmetries in gene flow and the frequency of reproductive isolating barriers vary in relation to mating system/s of the species pair. We combine these results with a simulation model and examples from the literature to address two general themes: (i) the two‐way interaction between introgression and the evolution of reproductive systems, and (ii) how mating system can facilitate or restrict interspecific gene flow. We conclude that examining mating system with hybridization provides unique opportunities to understand divergence and the processes underlying reproductive isolation.

Custom-size, functional, and durable DNA origami with design-specific scaffolds - FAS, Engelhardt; Praetorius, Florian M; Wachauf, CH; Brüggenthies, G; Kohler, F; Kick, B; Kadletz, KL; Pham, PN; Behler, KL; Gerling, T; Dietz, H (ACS Nano)
DNA origami nano-objects are usually designed around generic single-stranded “scaffolds”. Many properties of the target object are determined by details of those generic scaffold sequences. Here, we enable designers to fully specify the target structure not only in terms of desired 3D shape but also in terms of the sequences used. To this end, we built design tools to construct scaffold sequences de novo based on strand diagrams, and we developed scalable production methods for creating design-specific scaffold strands with fully user-defined sequences. We used 17 custom scaffolds having different lengths and sequence properties to study the influence of sequence redundancy and sequence composition on multilayer DNA origami assembly and to realize efficient one-pot assembly of multiscaffold DNA origami objects. Furthermore, as examples for functionalized scaffolds, we created a scaffold that enables direct, covalent cross-linking of DNA origami via UV irradiation, and we built DNAzyme-containing scaffolds that allow postfolding DNA origami domain separation.

The crossing Tverberg theorem - Fulek, Radoslav; Gärtner, Bernd; Kupavskii, Andrey; Valtr, Pavel; Wagner, Uli (35th International Symposium on Computational Geometry)
The Tverberg theorem is one of the cornerstones of discrete geometry. It states that, given a set X of at least (d+1)(r-1)+1 points in R^d, one can find a partition X=X_1 cup ... cup X_r of X, such that the convex hulls of the X_i, i=1,...,r, all share a common point. In this paper, we prove a strengthening of this theorem that guarantees a partition which, in addition to the above, has the property that the boundaries of full-dimensional convex hulls have pairwise nonempty intersections. Possible generalizations and algorithmic aspects are also discussed. As a concrete application, we show that any n points in the plane in general position span floor[n/3] vertex-disjoint triangles that are pairwise crossing, meaning that their boundaries have pairwise nonempty intersections; this number is clearly best possible. A previous result of Alvarez-Rebollar et al. guarantees floor[n/6] pairwise crossing triangles. Our result generalizes to a result about simplices in R^d,d >=2.

Why extension-based proofs fail - Alistarh, Dan-Adrian; Aspnes, James; Ellen, Faith; Gelashvili, Rati; Zhu, Leqi (Proceedings of the 51st Annual ACM SIGACT Symposium on Theory of Computing)
It is impossible to deterministically solve wait-free consensus in an asynchronous system. The classic proof uses a valency argument, which constructs an infinite execution by repeatedly extending a finite execution. We introduce extension-based proofs, a class of impossibility proofs that are modelled as an interaction between a prover and a protocol and that include valency arguments. Using proofs based on combinatorial topology, it has been shown that it is impossible to deterministically solve k-set agreement among n > k ≥ 2 processes in a wait-free manner. However, it was unknown whether proofs based on simpler techniques were possible. We show that this impossibility result cannot be obtained by an extension-based proof and, hence, extension-based proofs are limited in power.

Token swapping on trees - Biniaz, Ahmad; Jain, Kshitij; Lubiw, Anna; Masárová, Zuzana; Miltzow, Tillmann; Mondal, Debajyoti; Naredla, Anurag Murty; Tkadlec, Josef; Turcotte, Alexi (arXiv)
The input to the token swapping problem is a graph with vertices v1, v2, . . . , vn, and n tokens with labels 1,2, . . . , n, one on each vertex. The goal is to get token i to vertex vi for all i= 1, . . . , n using a minimum number of swaps, where a swap exchanges the tokens on the endpoints of an edge.Token swapping on a tree, also known as “sorting with a transposition tree,” is not known to be in P nor NP-complete. We present some partial results: 1. An optimum swap sequence may need to perform a swap on a leaf vertex that has the correct token (a “happy leaf”), disproving a conjecture of Vaughan. 2. Any algorithm that fixes happy leaves—as all known approximation algorithms for the problem do—has approximation factor at least 4/3. Furthermore, the two best-known 2-approximation algorithms have approximation factor exactly 2. 3. A generalized problem—weighted coloured token swapping—is NP-complete on trees, but solvable in polynomial time on paths and stars. In this version, tokens and vertices have colours, and colours have weights. The goal is to get every token to a vertex of the same colour, and the cost of a swap is the sum of the weights of the two tokens involved.

Sex-biased gene expression and dosage compensation on the Artemia franciscana Z-chromosome - Huylmans, Ann K; Toups, Melissa A; Macon, Ariana; Gammerdinger, William J; Vicoso, Beatriz (Genome biology and evolution)
Males and females of Artemia franciscana, a crustacean commonly used in the aquarium trade, are highly dimorphic. Sex is determined by a pair of ZW chromosomes, but the nature and extent of differentiation of these chromosomes is unknown. Here, we characterize the Z chromosome by detecting genomic regions that show lower genomic coverage in female than in male samples, and regions that harbor an excess of female-specific SNPs. We detect many Z-specific genes, which no longer have homologs on the W, but also Z-linked genes that appear to have diverged very recently from their existing W-linked homolog. We assess patterns of male and female expression in two tissues with extensive morphological dimorphism, gonads, and heads. In agreement with their morphology, sex-biased expression is common in both tissues. Interestingly, the Z chromosome is not enriched for sex-biased genes, and seems to in fact have a mechanism of dosage compensation that leads to equal expression in males and in females. Both of these patterns are contrary to most ZW systems studied so far, making A. franciscana an excellent model for investigating the interplay between the evolution of sexual dimorphism and dosage compensation, as well as Z chromosome evolution in general.

Data for the paper "Gene amplification as a form of population-level gene expression regulation" - Tomanek, Isabella
Organisms cope with change by employing transcriptional regulators. However, when faced with rare environments, the evolution of transcriptional regulators and their promoters may be too slow. We ask whether the intrinsic instability of gene duplication and amplification provides a generic alternative to canonical gene regulation. By real-time monitoring of gene copy number mutations in E. coli, we show that gene duplications and amplifications enable adaptation to fluctuating environments by rapidly generating copy number, and hence expression level, polymorphism. This ‘amplification-mediated gene expression tuning’ occurs on timescales similar to canonical gene regulation and can deal with rapid environmental changes. Mathematical modeling shows that amplifications also tune gene expression in stochastic environments where transcription factor-based schemes are hard to evolve or maintain. The fleeting nature of gene amplifications gives rise to a generic population-level mechanism that relies on genetic heterogeneity to rapidly tune expression of any gene, without leaving any genomic signature.
Keywords: Escherichia coli; gene amplification; galactose; DOG; experimental evolution; Illumina sequence data; FACS data; microfluidics data

Supplementary data for "Programming temporal morphing of self-actuated shells" - Guseinov, Ruslan

Supplementary data for "Sex-biased gene expression and dosage compensation on the Artemia franciscana Z-chromosome" (Huylman, Toups et al., 2019). - Vicoso, Beatriz

Supplementary data for the research paper "Haploinsufficiency of the intellectual disability gene SETD5 disturbs developmental gene expression and cognition" - Dotter, Christoph; Novarino, Gaia
This dataset contains the supplementary data for the research paper "Haploinsufficiency of the intellectual disability gene SETD5 disturbs developmental gene expression and cognition". The contained files have the following content: 'Supplementary Figures.pdf' Additional figures (as referenced in the paper). 'Supplementary Table 1. Statistics.xlsx' Details on statistical tests performed in the paper. 'Supplementary Table 2. Differentially expressed gene analysis.xlsx' Results for the differential gene expression analysis for embryonic (E9.5; analysis with edgeR) and in vitro (ESCs, EBs, NPCs; analysis with DESeq2) samples. 'Supplementary Table 3. Gene Ontology (GO) term enrichment analysis.xlsx' Results for the GO term enrichment analysis for differentially expressed genes in embryonic (GO E9.5) and in vitro (GO ESC, GO EBs, GO NPCs) samples. Differentially expressed genes for in vitro samples were split into upregulated and downregulated genes (up/down) and the analysis was performed on each subset (e.g. GO ESC up / GO ESC down). 'Supplementary Table 4. Differentially expressed gene analysis for CFC samples.xlsx' Results for the differential gene expression analysis for samples from adult mice before (HC - Homecage) and 1h and 3h after contextual fear conditioning (1h and 3h, respectively). Each sheet shows the results for a different comparison. Sheets 1-3 show results for comparisons between timepoints for wild type (WT) samples only and sheets 4-6 for the same comparisons in mutant (Het) samples. Sheets 7-9 show results for comparisons between genotypes at each time point and sheet 10 contains the results for the analysis of differential expression trajectories between wild type and mutant. 'Supplementary Table 5. Cluster identification.xlsx' Results for k-means clustering of genes by expression. Sheet 1 shows clustering of just the genes with significantly different expression trajectories between genotypes. Sheet 2 shows clustering of all genes that are significantly differentially expressed in any of the comparisons (includes also genes with same trajectories). 'Supplementary Table 6. GO term cluster analysis.xlsx' Results for the GO term enrichment analysis and EWCE analysis for enrichment of cell type specific genes for each cluster identified by clustering genes with different expression trajectories (see Table S5, sheet 1). 'Supplementary Table 7. Setd5 mass spectrometry results.xlsx' Results showing proteins interacting with Setd5 as identified by mass spectrometry. Sheet 1 shows protein protein interaction data generated from these results (combined with data from the STRING database. Sheet 2 shows the results of the statistical analysis with limma. 'Supplementary Table 8. PolII ChIP-seq analysis.xlsx' Results for the Chip-Seq analysis for binding of RNA polymerase II (PolII). Sheet 1 shows results for differential binding of PolII at the transcription start site (TSS) between genotypes and sheets 2+3 show the corresponding GO enrichment analysis for these differentially bound genes. Sheet 4 shows RNAseq counts for genes with increased binding of PolII at the TSS.

Supplementary Code and Data for the paper "The Entorhinal Cognitive Map is Attracted to Goals" - Nardin, Michele
Open the files in Jupyter Notebook (reccomended https://www.anaconda.com/distribution/#download-section with Python 3.7).

Pleiotropy modulates the efficacy of selection in drosophila melanogaster - Fraisse, Christelle; Puixeu Sala, Gemma; Vicoso, Beatriz (Molecular biology and evolution)
Pleiotropy is the well-established idea that a single mutation affects multiple phenotypes. If a mutation has opposite effects on fitness when expressed in different contexts, then genetic conflict arises. Pleiotropic conflict is expected to reduce the efficacy of selection by limiting the fixation of beneficial mutations through adaptation, and the removal of deleterious mutations through purifying selection. Although this has been widely discussed, in particular in the context of a putative “gender load,” it has yet to be systematically quantified. In this work, we empirically estimate to which extent different pleiotropic regimes impede the efficacy of selection in Drosophila melanogaster. We use whole-genome polymorphism data from a single African population and divergence data from D. simulans to estimate the fraction of adaptive fixations (α), the rate of adaptation (ωA), and the direction of selection (DoS). After controlling for confounding covariates, we find that the different pleiotropic regimes have a relatively small, but significant, effect on selection efficacy. Specifically, our results suggest that pleiotropic sexual antagonism may restrict the efficacy of selection, but that this conflict can be resolved by limiting the expression of genes to the sex where they are beneficial. Intermediate levels of pleiotropy across tissues and life stages can also lead to maladaptation in D. melanogaster, due to inefficient purifying selection combined with low frequency of mutations that confer a selective advantage. Thus, our study highlights the need to consider the efficacy of selection in the context of antagonistic pleiotropy, and of genetic conflict in general.

From Dyson to Pearcey: Universal statistics in random matrix theory - Schröder, Dominik J
In the first part of this thesis we consider large random matrices with arbitrary expectation and a general slowly decaying correlation among its entries. We prove universality of the local eigenvalue statistics and optimal local laws for the resolvent in the bulk and edge regime. The main novel tool is a systematic diagrammatic control of a multivariate cumulant expansion. In the second part we consider Wigner-type matrices and show that at any cusp singularity of the limiting eigenvalue distribution the local eigenvalue statistics are uni- versal and form a Pearcey process. Since the density of states typically exhibits only square root or cubic root cusp singularities, our work complements previous results on the bulk and edge universality and it thus completes the resolution of the Wigner- Dyson-Mehta universality conjecture for the last remaining universality type. Our analysis holds not only for exact cusps, but approximate cusps as well, where an ex- tended Pearcey process emerges. As a main technical ingredient we prove an optimal local law at the cusp, and extend the fast relaxation to equilibrium of the Dyson Brow- nian motion to the cusp regime. In the third and final part we explore the entrywise linear statistics of Wigner ma- trices and identify the fluctuations for a large class of test functions with little regularity. This enables us to study the rectangular Young diagram obtained from the interlacing eigenvalues of the random matrix and its minor, and we find that, despite having the same limit, the fluctuations differ from those of the algebraic Young tableaux equipped with the Plancharel measure.

KS(conf): A light-weight test if a ConvNet operates outside of Its specifications - Sun, Rémy; Lampert, Christoph
Computer vision systems for automatic image categorization have become accurate and reliable enough that they can run continuously for days or even years as components of real-world commercial applications. A major open problem in this context, however, is quality control. Good classification performance can only be expected if systems run under the specific conditions, in particular data distributions, that they were trained for. Surprisingly, none of the currently used deep network architectures have a built-in functionality that could detect if a network operates on data from a distribution it was not trained for, such that potentially a warning to the human users could be triggered. In this work, we describe KS(conf), a procedure for detecting such outside of specifications (out-of-specs) operation, based on statistical testing of the network outputs. We show by extensive experiments using the ImageNet, AwA2 and DAVIS datasets on a variety of ConvNets architectures that KS(conf) reliably detects out-of-specs situations. It furthermore has a number of properties that make it a promising candidate for practical deployment: it is easy to implement, adds almost no overhead to the system, works with all networks, including pretrained ones, and requires no a priori knowledge of how the data distribution could change.

On diffusive variants of some classical viscoelastic rate-type models - Dostalík, Mark; Pruša, Vít; Skrivan, Tomas (AIP Conference Proceedings)
We present a thermodynamically based approach to the design of models for viscoelastic fluids with stress diffusion effect. In particular, we show how to add a stress diffusion term to some standard viscoelastic rate-type models (Giesekus, FENE-P, Johnson–Segalman, Phan-Thien–Tanner and Bautista–Manero–Puig) so that the resulting models with the added stress diffusion term are thermodynamically consistent in the sense that they obey the first and the second law of thermodynamics. We point out the potential applications of the provided thermodynamical background in the study of flows of fluids described by the proposed models.

Introduction to the Special Collection: International Congress on Mathematical Physics (ICMP) 2018 - Jaksic, Vojkan; Seiringer, Robert (Journal of Mathematical Physics)

In-medium bound states of two bosonic impurities in a one-dimensional Fermi gas - Huber, D.; Hammer, H.-W.; Volosniev, Artem (Physical Review Research)
We investigate the ground-state energy of a one-dimensional Fermi gas with two bosonic impurities. We consider spinless fermions with no fermion-fermion interactions. The fermion-impurity and impurity-impurity interactions are modeled with Dirac delta functions. First, we study the case where impurity and fermion have equal masses, and the impurity-impurity two-body interaction is identical to the fermion-impurity interaction, such that the system is solvable with the Bethe ansatz. For attractive interactions, we find that the energy of the impurity-impurity subsystem is below the energy of the bound state that exists without the Fermi gas. We interpret this as a manifestation of attractive boson-boson interactions induced by the fermionic medium, and refer to the impurity-impurity subsystem as an in-medium bound state. For repulsive interactions, we find no in-medium bound states. Second, we construct an effective model to describe these interactions, and compare its predictions to the exact solution. We use this effective model to study nonintegrable systems with unequal masses and/or potentials. We discuss parameter regimes for which impurity-impurity attraction induced by the Fermi gas can lead to the formation of in-medium bound states made of bosons that repel each other in the absence of the Fermi gas.

Emergent SU(2) dynamics and perfect quantum many-body scars - Choi, Soonwon; Turner, Christopher J.; Pichler, Hannes; Ho, Wen Wei; Michailidis, Alexios; Papić, Zlatko; Serbyn, Maksym; Lukin, Mikhail D.; Abanin, Dmitry A. (Physical Review Letters)
Motivated by recent experimental observations of coherent many-body revivals in a constrained Rydbergatom chain, we construct a weak quasilocal deformation of the Rydberg-blockaded Hamiltonian, whichmakes the revivals virtually perfect. Our analysis suggests the existence of an underlying nonintegrableHamiltonian which supports an emergent SU(2)-spin dynamics within a small subspace of the many-bodyHilbert space. We show that such perfect dynamics necessitates the existence of atypical, nonergodicenergy eigenstates—quantum many-body scars. Furthermore, using these insights, we construct a toymodel that hosts exact quantum many-body scars, providing an intuitive explanation of their origin. Ourresults offer specific routes to enhancing coherent many-body revivals and provide a step towardestablishing the stability of quantum many-body scars in the thermodynamic limit.

Quantum many-body dynamics of the Einstein-de Haas effect - Mentink, Johann H; Katsnelson, Mikhail; Lemeshko, Mikhail (Physical Review B)
In 1915, Einstein and de Haas and Barnett demonstrated that changing the magnetization of a magnetic material results in mechanical rotation and vice versa. At the microscopic level, this effect governs the transfer between electron spin and orbital angular momentum, and lattice degrees of freedom, understanding which is key for molecular magnets, nano-magneto-mechanics, spintronics, and ultrafast magnetism. Until now, the timescales of electron-to-lattice angular momentum transfer remain unclear, since modeling this process on a microscopic level requires the addition of an infinite amount of quantum angular momenta. We show that this problem can be solved by reformulating it in terms of the recently discovered angulon quasiparticles, which results in a rotationally invariant quantum many-body theory. In particular, we demonstrate that nonperturbative effects take place even if the electron-phonon coupling is weak and give rise to angular momentum transfer on femtosecond timescales.

Receptor crosstalk improves concentration sensing of multiple ligands - Carballo-Pacheco, Martín; Desponds, Jonathan; Gavrilchenko, Tatyana; Mayer, Andreas; Prizak, Roshan; Reddy, Gautam; Nemenman, Ilya; Mora, Thierry (Physical Review E)
Cells need to reliably sense external ligand concentrations to achieve various biological functions such as chemotaxis or signaling. The molecular recognition of ligands by surface receptors is degenerate in many systems, leading to crosstalk between ligand-receptor pairs. Crosstalk is often thought of as a deviation from optimal specific recognition, as the binding of noncognate ligands can interfere with the detection of the receptor's cognate ligand, possibly leading to a false triggering of a downstream signaling pathway. Here we quantify the optimal precision of sensing the concentrations of multiple ligands by a collection of promiscuous receptors. We demonstrate that crosstalk can improve precision in concentration sensing and discrimination tasks. To achieve superior precision, the additional information about ligand concentrations contained in short binding events of the noncognate ligand should be exploited. We present a proofreading scheme to realize an approximate estimation of multiple ligand concentrations that reaches a precision close to the derived optimal bounds. Our results help rationalize the observed ubiquity of receptor crosstalk in molecular sensing.

Attractive dipolar coupling between stacked exciton fluids - Hubert, Colin; Baruchi, Yifat; Mazuz-Harpaz, Yotam; Cohen, Kobi; Biermann, Klaus; Lemeshko, Mikhail; West, Ken; Pfeiffer, Loren; Rapaport, Ronen; Santos, Paulo (Physical Review X)
Dipolar coupling plays a fundamental role in the interaction between electrically or magnetically polarized species such as magnetic atoms and dipolar molecules in a gas or dipolar excitons in the solid state. Unlike Coulomb or contactlike interactions found in many atomic, molecular, and condensed-matter systems, this interaction is long-ranged and highly anisotropic, as it changes from repulsive to attractive depending on the relative positions and orientation of the dipoles. Because of this unique property, many exotic, symmetry-breaking collective states have been recently predicted for cold dipolar gases, but only a few have been experimentally detected and only in dilute atomic dipolar Bose-Einstein condensates. Here, we report on the first observation of attractive dipolar coupling between excitonic dipoles using a new design of stacked semiconductor bilayers. We show that the presence of a dipolar exciton fluid in one bilayer modifies the spatial distribution and increases the binding energy of excitonic dipoles in a vertically remote layer. The binding energy changes are explained using a many-body polaron model describing the deformation of the exciton cloud due to its interaction with a remote dipolar exciton. The surprising nonmonotonic dependence on the cloud density indicates the important role of dipolar correlations, which is unique to dense, strongly interacting dipolar solid-state systems. Our concept provides a route for the realization of dipolar lattices with strong anisotropic interactions in semiconductor systems, which open the way for the observation of theoretically predicted new and exotic collective phases, as well as for engineering and sensing their collective excitations.

Probing the many-body localization phase transition with superconducting circuits - Orell, Tuure; Michailidis, Alexios; Serbyn, Maksym; Silveri, Matti (Physical Review B)
Chains of superconducting circuit devices provide a natural platform for studies of synthetic bosonic quantum matter. Motivated by the recent experimental progress in realizing disordered and interacting chains of superconducting transmon devices, we study the bosonic many-body localization phase transition using the methods of exact diagonalization as well as matrix product state dynamics. We estimate the location of transition separating the ergodic and the many-body localized phases as a function of the disorder strength and the many-body on-site interaction strength. The main difference between the bosonic model realized by superconducting circuits and similar fermionic model is that the effect of the on-site interaction is stronger due to the possibility of multiple excitations occupying the same site. The phase transition is found to be robust upon including longer-range hopping and interaction terms present in the experiments. Furthermore, we calculate experimentally relevant local observables and show that their temporal fluctuations can be used to distinguish between the dynamics of Anderson insulator, many-body localization, and delocalized phases. While we consider unitary dynamics, neglecting the effects of dissipation, decoherence, and measurement back action, the timescales on which the dynamics is unitary are sufficient for observation of characteristic dynamics in the many-body localized phase. Moreover, the experimentally available disorder strength and interactions allow for tuning the many-body localization phase transition, thus making the arrays of superconducting circuit devices a promising platform for exploring localization physics and phase transition.

Effect of anomalous diffusion of fluctuating Cooper pairs on the density of states of superconducting NbN thin films - Brighi, Pietro; Grilli, Marco; Leridon, Brigitte; Caprara, Sergio (Physical Review B)
Recent scanning tunneling microscopy experiments in NbN thin disordered superconducting films found an emergent inhomogeneity at the scale of tens of nanometers. This inhomogeneity is mirrored by an apparent dimensional crossover in the paraconductivity measured in transport above the superconducting critical temperature Tc. This behavior was interpreted in terms of an anomalous diffusion of fluctuating Cooper pairs that display a quasiconfinement (i.e., a slowing down of their diffusive dynamics) on length scales shorter than the inhomogeneity identified by tunneling experiments. Here, we assume this anomalous diffusive behavior of fluctuating Cooper pairs and calculate the effect of these fluctuations on the electron density of states above Tc. We find that the density of states is substantially suppressed up to temperatures well above Tc. This behavior, which is closely reminiscent of a pseudogap, only arises from the anomalous diffusion of fluctuating Cooper pairs in the absence of stable preformed pairs, setting the stage for an intermediate behavior between the two common paradigms in the superconducting-insulator transition, namely, the localization of Cooper pairs (the so-called bosonic scenario) and the breaking of Cooper pairs into unpaired electrons due to strong disorder (the so-called fermionic scenario).

Heteroclinic and homoclinic connections in a Kolmogorov-like flow - Suri, Balachandra; Pallantla, Ravi Kumar; Schatz, Michael F.; Grigoriev, Roman O. (Physical Review E)
Recent studies suggest that unstable recurrent solutions of the Navier-Stokes equation provide new insights into dynamics of turbulent flows. In this study, we compute an extensive network of dynamical connections between such solutions in a weakly turbulent quasi-two-dimensional Kolmogorov flow that lies in the inversion symmetric subspace. In particular, we find numerous isolated heteroclinic connections between different types of solutions—equilibria, periodic, and quasiperiodic orbits—as well as continua of connections forming higher-dimensional connecting manifolds. We also compute a homoclinic connection of a periodic orbit and provide strong evidence that the associated homoclinic tangle forms the chaotic repeller that underpins transient turbulence in the symmetric subspace.

Floating Wigner crystal with no boundary charge fluctuations - Lewin, Mathieu; Lieb, Elliott H.; Seiringer, Robert (Physical Review B)
We modify the "floating crystal" trial state for the classical homogeneous electron gas (also known as jellium), in order to suppress the boundary charge fluctuations that are known to lead to a macroscopic increase of the energy. The argument is to melt a thin layer of the crystal close to the boundary and consequently replace it by an incompressible fluid. With the aid of this trial state we show that three different definitions of the ground-state energy of jellium coincide. In the first point of view the electrons are placed in a neutralizing uniform background. In the second definition there is no background but the electrons are submitted to the constraint that their density is constant, as is appropriate in density functional theory. Finally, in the third system each electron interacts with a periodic image of itself; that is, periodic boundary conditions are imposed on the interaction potential.

End-to-end correlated subgap states in hybrid nanowires - Anselmetti, G. L. R.; Martinez, E. A.; Ménard, G. C.; Puglia, D.; Malinowski, F. K.; Lee, J. S.; Choi, S.; Pendharkar, M.; Palmstrøm, C. J.; Marcus, C. M.; Casparis, L.; Higginbotham, Andrew P (Physical Review B)
End-to-end correlated bound states are investigated in superconductor-semiconductor hybrid nanowires at zero magnetic field. Peaks in subgap conductance are independently identified from each wire end, and a cross-correlation function is computed that counts end-to-end coincidences, averaging over thousands of subgap features. Strong correlations in a short, 300-nm device are reduced by a factor of 4 in a long, 900-nm device. In addition, subgap conductance distributions are investigated, and correlations between the left and right distributions are identified based on their mutual information.

Analytically solvable renormalization group for the many-body localization transition - Goremykina, Anna; Vasseur, Romain; Serbyn, Maksym (Physical Review Letters)
We introduce a simple, exactly solvable strong-randomness renormalization group (RG) model for the many-body localization (MBL) transition in one dimension. Our approach relies on a family of RG flows parametrized by the asymmetry between thermal and localized phases. We identify the physical MBL transition in the limit of maximal asymmetry, reflecting the instability of MBL against rare thermal inclusions. We find a critical point that is localized with power-law distributed thermal inclusions. The typical size of critical inclusions remains finite at the transition, while the average size is logarithmically diverging. We propose a two-parameter scaling theory for the many-body localization transition that falls into the Kosterlitz-Thouless universality class, with the MBL phase corresponding to a stable line of fixed points with multifractal behavior.

Coupled superfluidity of binary Bose mixtures in two dimensions - Karle, Volker; Defenu, Nicolò; Enss, Tilman (Physical Review A)
We consider a two-component Bose gas in two dimensions at a low temperature with short-range repulsive interaction. In the coexistence phase where both components are superfluid, interspecies interactions induce a nondissipative drag between the two superfluid flows (Andreev-Bashkin effect). We show that this behavior leads to a modification of the usual Berezinskii-Kosterlitz-Thouless (BKT) transition in two dimensions. We extend the renormalization of the superfluid densities at finite temperature using the renormalization-group approach and find that the vortices of one component have a large influence on the superfluid properties of the other, mediated by the nondissipative drag. The extended BKT flow equations indicate that the occurrence of the vortex unbinding transition in one of the components can induce the breakdown of superfluidity also in the other, leading to a locking phenomenon for the critical temperatures of the two gases.

Quantum control of molecular rotation - Koch, Christiane P.; Lemeshko, Mikhail; Sugny, Dominique (Reviews of Modern Physics)
The angular momentum of molecules, or, equivalently, their rotation in three-dimensional space, is ideally suited for quantum control. Molecular angular momentum is naturally quantized, time evolution is governed by a well-known Hamiltonian with only a few accurately known parameters, and transitions between rotational levels can be driven by external fields from various parts of the electromagnetic spectrum. Control over the rotational motion can be exerted in one-, two-, and many-body scenarios, thereby allowing one to probe Anderson localization, target stereoselectivity of bimolecular reactions, or encode quantum information to name just a few examples. The corresponding approaches to quantum control are pursued within separate, and typically disjoint, subfields of physics, including ultrafast science, cold collisions, ultracold gases, quantum information science, and condensed-matter physics. It is the purpose of this review to present the various control phenomena, which all rely on the same underlying physics, within a unified framework. To this end, recall the Hamiltonian for free rotations, assuming the rigid rotor approximation to be valid, and summarize the different ways for a rotor to interact with external electromagnetic fields. These interactions can be exploited for control—from achieving alignment, orientation, or laser cooling in a one-body framework, steering bimolecular collisions, or realizing a quantum computer or quantum simulator in the many-body setting.

A tight upper bound on mutual information - Hledik, Michal; Sokolowski, Thomas R; Tkačik, Gašper (IEEE Information Theory Workshop, ITW 2019)
We derive a tight lower bound on equivocation (conditional entropy), or equivalently a tight upper bound on mutual information between a signal variable and channel outputs. The bound is in terms of the joint distribution of the signals and maximum a posteriori decodes (most probable signals given channel output). As part of our derivation, we describe the key properties of the distribution of signals, channel outputs and decodes, that minimizes equivocation and maximizes mutual information. This work addresses a problem in data analysis, where mutual information between signals and decodes is sometimes used to lower bound the mutual information between signals and channel outputs. Our result provides a corresponding upper bound.

Fast approximate shortest paths in the congested clique - Censor-Hillel, Keren; Dory, Michal; Korhonen, Janne; Leitersdorf, Dean (Proceedings of the 2019 ACM Symposium on Principles of Distributed Computin)
We design fast deterministic algorithms for distance computation in the CONGESTED CLIQUE model. Our key contributions include: - A (2+ε)-approximation for all-pairs shortest paths problem in O(log²n / ε) rounds on unweighted undirected graphs. With a small additional additive factor, this also applies for weighted graphs. This is the first sub-polynomial constant-factor approximation for APSP in this model. - A (1+ε)-approximation for multi-source shortest paths problem from O(√n) sources in O(log² n / ε) rounds on weighted undirected graphs. This is the first sub-polynomial algorithm obtaining this approximation for a set of sources of polynomial size. Our main techniques are new distance tools that are obtained via improved algorithms for sparse matrix multiplication, which we leverage to construct efficient hopsets and shortest paths. Furthermore, our techniques extend to additional distance problems for which we improve upon the state-of-the-art, including diameter approximation, and an exact single-source shortest paths algorithm for weighted undirected graphs in Õ(n^{1/6}) rounds.

Protein dynamics regulate distinct biochemical properties of cryptochromes in mammalian circadian rhythms - Fribourgh, Jennifer L.; Srivastava, Ashutosh; Sandate, Colby R.; Michael, Alicia; Hsu, Peter L.; Rakers, Christin; Nguyen, Leslee T.; Torgrimson, Megan R.; Parico, Gian Carlo G.; Tripathi, Sarvind; Zheng, Ning; Lander, Gabriel C.; et al. (bioRxiv)
Circadian rhythms are generated by a transcription-based feedback loop where CLOCK:BMAL1 drive transcription of their repressors (PER1/2, CRY1/2), which bind to CLOCK:BMAL1 to close the feedback loop with ~24-hour periodicity. Here we identify a key biochemical and structural difference between CRY1 and CRY2 that underlies their differential strengths as transcriptional repressors. While both cryptochromes bind the BMAL1 transactivation domain with similar affinity to sequester it from coactivators, CRY1 is recruited with much higher affinity to the PAS domain core of CLOCK:BMAL1, allowing it to serve as a stronger repressor that lengthens circadian period. We identify a dynamic loop in the secondary pocket that regulates differential binding of cryptochromes to the PAS domain core. Notably, PER2 binding remodels this loop in CRY2 to enhance its affinity for CLOCK:BMAL1, explaining why CRY2 forms an obligate heterodimer with PER2, while CRY1 is capable of repressing CLOCK:BMAL1 both with and without PER2.

A massive magnetic helium atmosphere white dwarf binary in a young star cluster - Richer, Harvey B.; Kerr, Ronan; Heyl, Jeremy; Caiazzo, Ilaria; Cummings, Jeffrey; Bergeron, Pierre; Dufour, Patrick (The Astrophysical Journal)
We have searched the Gaia DR2 catalog for previously unknown hot white dwarfs in the direction of young open star clusters. The aim of this experiment was to try and extend the initial–final mass relation (IFMR) to somewhat higher masses, potentially challenging the Chandrasekhar limit currently thought to be around 1.38 M⊙. We discovered a particularly interesting white dwarf in the direction of the young ∼150 Myr old cluster Messier 47 (NGC 2422). All Gaia indicators (proper motion, parallax, location in the Gaia color–magnitude diagram) suggest that it is a cluster member. Its spectrum, obtained from Gemini-South, yields a number of anomalies: it is a DB (helium-rich atmosphere) white dwarf, it has a large magnetic field (2.5 MG), is of high mass (∼1.06 M⊙), and its colors are very peculiar—particularly the redder ones (r, i, z and y), which suggests that it may have a late-type companion. This may be the only magnetized, detached binary white dwarf with a non-degenerate companion of any spectral type known in or out of a star cluster. If the white dwarf is a cluster member, as all indicators suggest, its progenitor had a mass just over 6 M⊙. It may, however, be telling an even more interesting story than the one related to the IFMR, one about the origin of stellar magnetic fields, SNe I, and gravitational waves from low-mass stellar systems.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

A multimass velocity dispersion model of 47 Tucanae indicates no evidence for an intermediate-mass black hole - Mann, Christopher R.; Richer, Harvey; Heyl, Jeremy; Anderson, Jay; Kalirai, Jason; Caiazzo, Ilaria; Möhle, Swantje D.; Knee, Alan; Baumgardt, Holger (The Astrophysical Journal)
In this paper, we analyze stellar proper motions in the core of the globular cluster 47 Tucanae to explore the possibility of an intermediate-mass black hole (IMBH) influence on the stellar dynamics. Our use of short-wavelength photometry affords us an exceedingly clear view of stellar motions into the very center of the crowded core, yielding proper motions for >50,000 stars in the central 2′. We model the velocity dispersion profile of the cluster using an isotropic Jeans model. The density distribution is taken as a central IMBH point mass added to a combination of King templates. We individually model the general low-mass cluster objects (main sequence/giant stars), as well as the concentrated populations of heavy binary systems and dark stellar remnants. Using unbinned likelihood model fitting, we find that the inclusion of the concentrated populations in our model plays a crucial role in fitting for an IMBH mass. The concentrated binaries and stellar-mass black holes (BHs) produce a sufficient velocity dispersion signal in the core so as to make an IMBH unnecessary to fit the observations. We additionally determine that a stellar-mass BH retention fraction of 8.5% becomes incompatible with our observed velocities in the core.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Quantitative investigation of gene expression principles through combinatorial drug perturbation and theory - Lukacisin, Martin
The regulation of gene expression is one of the most fundamental processes in living systems. In recent years, thanks to advances in sequencing technology and automation, it has become possible to study gene expression quantitatively, genome-wide and in high-throughput. This leads to the possibility of exploring changes in gene expression in the context of many external perturbations and their combinations, and thus of characterising the basic principles governing gene regulation. In this thesis, I present quantitative experimental approaches to studying transcriptional and protein level changes in response to combinatorial drug treatment, as well as a theoretical data-driven approach to analysing thermodynamic principles guiding transcription of protein coding genes. In the first part of this work, I present a novel methodological framework for quantifying gene expression changes in drug combinations, termed isogrowth profiling. External perturbations through small molecule drugs influence the growth rate of the cell, leading to wide-ranging changes in cellular physiology and gene expression. This confounds the gene expression changes specifically elicited by the particular drug. Combinatorial perturbations, owing to the increased stress they exert, influence the growth rate even more strongly and hence suffer the convolution problem to a greater extent when measuring gene expression changes. Isogrowth profiling is a way to experimentally abstract non-specific, growth rate related changes, by performing the measurement using varying ratios of two drugs at such concentrations that the overall inhibition rate is constant. Using a robotic setup for automated high-throughput re-dilution culture of Saccharomyces cerevisiae, the budding yeast, I investigate all pairwise interactions of four small molecule drugs through sequencing RNA along a growth isobole. Through principal component analysis, I demonstrate here that isogrowth profiling can uncover drug-specific as well as drug-interaction-specific gene expression changes. I show that drug-interaction-specific gene expression changes can be used for prediction of higher-order drug interactions. I propose a simplified generalised framework of isogrowth profiling, with few measurements needed for each drug pair, enabling the broad application of isogrowth profiling to high-throughput screening of inhibitors of cellular growth and beyond. Such high-throughput screenings of gene expression changes specific to pairwise drug interactions will be instrumental for predicting the higher-order interactions of the drugs. In the second part of this work, I extend isogrowth profiling to single-cell measurements of gene expression, characterising population heterogeneity in the budding yeast in response to combinatorial drug perturbation while controlling for non-specific growth rate effects. Through flow cytometry of strains with protein products fused to green fluorescent protein, I discover multiple proteins with bi-modally distributed expression levels in the population in response to drug treatment. I characterize more closely the effect of an ionic stressor, lithium chloride, and find that it inhibits the splicing of mRNA, most strongly affecting ribosomal protein transcripts and leading to a bi-stable behaviour of a small ribosomal subunit protein Rps22B. Time-lapse microscopy of a microfluidic culture system revealed that the induced Rps22B heterogeneity leads to preferential survival of Rps22B-low cells after long starvation, but to preferential proliferation of Rps22B-high cells after short starvation. Overall, this suggests that yeast cells might use splicing of ribosomal genes for bet-hedging in fluctuating environments. I give specific examples of how further exploration of cellular heterogeneity in yeast in response to external perturbation has the potential to reveal yet-undiscovered gene regulation circuitry. In the last part of this thesis, a re-analysis of a published sequencing dataset of nascent elongating transcripts is used to characterise the thermodynamic constraints for RNA polymerase II (RNAP) elongation. Population-level data on RNAP position throughout the transcribed genome with single nucleotide resolution are used to infer the sequence specific thermodynamic determinants of RNAP pausing and backtracking. This analysis reveals that the basepairing strength of the eight nucleotide-long RNA:DNA duplex relative to the basepairing strength of the same sequence when in DNA:DNA duplex, and the change in this quantity during RNA polymerase movement, is the key determinant of RNAP pausing. This is true for RNAP pausing while elongating, but also of RNAP pausing while backtracking and of the backtracking length. The quantitative dependence of RNAP pausing on basepairing energetics is used to infer the increase in pausing due to transcriptional mismatches, leading to a hypothesis that pervasive RNA polymerase II pausing is due to basepairing energetics, as an evolutionary cost for increased RNA polymerase II fidelity. This work advances our understanding of the general principles governing gene expression, with the goal of making computational predictions of single-cell gene expression responses to combinatorial perturbations based on the individual perturbations possible. This ability would substantially facilitate the design of drug combination treatments and, in the long term, lead to our increased ability to more generally design targeted manipulations to any biological system.

Collective defenses of garden ants against a fungal pathogen - Casillas Perez, Barbara E
Social insect colonies tend to have numerous members which function together like a single organism in such harmony that the term ``super-organism'' is often used. In this analogy the reproductive caste is analogous to the primordial germ cells of a metazoan, while the sterile worker caste corresponds to somatic cells. The worker castes, like tissues, are in charge of all functions of a living being, besides reproduction. The establishment of new super-organismal units (i.e. new colonies) is accomplished by the co-dependent castes. The term oftentimes goes beyond a metaphor. We invoke it when we speak about the metabolic rate, thermoregulation, nutrient regulation and gas exchange of a social insect colony. Furthermore, we assert that the super-organism has an immune system, and benefits from ``social immunity''. Social immunity was first summoned by evolutionary biologists to resolve the apparent discrepancy between the expected high frequency of disease outbreak amongst numerous, closely related tightly-interacting hosts, living in stable and microbially-rich environments, against the exceptionally scarce epidemic accounts in natural populations. Social immunity comprises a multi-layer assembly of behaviours which have evolved to effectively keep the pathogenic enemies of a colony at bay. The field of social immunity has drawn interest, as it becomes increasingly urgent to stop the collapse of pollinator species and curb the growth of invasive pests. In the past decade, several mechanisms of social immune responses have been dissected, but many more questions remain open. I present my work in two experimental chapters. In the first, I use invasive garden ants (*Lasius neglectus*) to study how pathogen load and its distribution among nestmates affect the grooming response of the group. Any given group of ants will carry out the same total grooming work, but will direct their grooming effort towards individuals carrying a relatively higher spore load. Contrary to expectation, the highest risk of transmission does not stem from grooming highly contaminated ants, but instead, we suggest that the grooming response likely minimizes spore loss to the environment, reducing contamination from inadvertent pickup from the substrate. The second is a comparative developmental approach. I follow black garden ant queens (*Lasius niger*) and their colonies from mating flight, through hibernation for a year. Colonies which grow fast from the start, have a lower chance of survival through hibernation, and those which survive grow at a lower pace later. This is true for colonies of naive and challenged queens. Early pathogen exposure of the queens changes colony dynamics in an unexpected way: colonies from exposed queens are more likely to grow slowly and recover in numbers only after they survive hibernation. In addition to the two experimental chapters, this thesis includes a co-authored published review on organisational immunity, where we enlist the experimental evidence and theoretical framework on which this hypothesis is built, identify the caveats and underline how the field is ripe to overcome them. In a final chapter, I describe my part in two collaborative efforts, one to develop an image-based tracker, and the second to develop a classifier for ant behaviour.
Keywords: Social Immunity; Sanitary care; Social Insects; Organisational Immunity; Colony development; Multi-target tracking

Clathrin-Mediated endocytosis, post-endocytic trafficking and their regulatory controls in plants - Narasimhan, Madhumitha
Clathrin-Mediated Endocytosis (CME) is an aspect of cellular trafficking that is constantly regulated for mediating developmental and physiological responses. The main aim of my thesis is to decipher the basic mechanisms of CME and post-endocytic trafficking in the whole multicellular organ systems of Arabidopsis. The first chapter of my thesis describes the search for new components involved in CME. Tandem affinity purification was conducted using CLC and its interacting partners were identified. Amongst the identified proteins were the Auxilin-likes1 and 2 (Axl1/2), putative uncoating factors, for which we made a full functional analysis. Over-expression of Axl1/2 causes extreme modifications in the dynamics of the machinery proteins and inhibition of endocytosis altogether. However the loss of function of the axl1/2 did not present any cellular or physiological phenotype, meaning Auxilin-likes do not form the major uncoating machinery. The second chapter of my thesis describes the establishment/utilisation of techniques to capture the dynamicity and the complexity of CME and post-endocytic trafficking. We have studied the development of endocytic pits at the PM – specifically, the mode of membrane remodeling during pit development and the role of actin in it, given plant cells possess high turgor pressure. Utilizing the improved z-resolution of TIRF and VAEM techniques, we captured the time-lapse of the endocytic events at the plasma membrane; and using particle detection software, we quantitatively analysed all the endocytic trajectories in an unbiased way to obtain the endocytic rate of the system. This together with the direct analysis of cargo internalisation from the PM provided an estimate on the endocytic potential of the cell. We also developed a methodology for ultrastructural analysis of different populations of Clathrin-Coated Structures (CCSs) in both PM and endomembranes in unroofed protoplasts. Structural analysis, together with the intensity profile of CCSs at the PM show that the mode of CCP development at the PM follows ‘Constant curvature model’; meaning that clathrin polymerisation energy is a major contributing factor of membrane remodeling. In addition, other analyses clearly show that actin is not required for membrane remodeling during invagination or any other step of CCP development, despite the prevalent high turgor pressure. However, actin is essential in orchestrating the post-endocytic trafficking of CCVs facilitating the EE formation. We also observed that the uncoating process post-endocytosis is not immediate; an alternative mechanism of uncoating – Sequential multi-step process – functions in the cell. Finally we also looked at one of the important physiological stimuli modulating the process – hormone, auxin. auxin has been known to influence CME before. We have made a detailed study on the concentration-time based effect of auxin on the machinery proteins, CCP development, and the specificity of cargoes endocytosed. To this end, we saw no general effect of auxin on CME at earlier time points. However, very low concentration of IAA, such as 50nM, accelerates endocytosis of specifically PIN2 through CME. Such a tight regulatory control with high specificity to PIN2 could be essential in modulating its polarity.

Functional analysis of the docked vesicle pool in hippocampal mossy fiber terminals by electron microscopy - Kim, Olena; Borges Merjane, Carolina; Jonas, Peter M (Intrinsic Activity)
Keywords: hippocampus; mossy fibers; readily releasable pool; electron microscopy

Lymph node mechanics: Deciphering the interplay between stroma contractility, morphology and lymphocyte trafficking - Assen, Frank P
Lymph nodes are es s ential organs of the immune s ys tem where adaptive immune responses originate, and consist of various leukocyte populations and a stromal backbone. Fibroblastic reticular cells (FRCs) are the main stromal cells and form a sponge-like extracellular matrix network, called conduits , which they thems elves enwrap and contract. Lymph, containing s oluble antigens , arrive in lymph nodes via afferent lymphatic vessels that connect to the s ubcaps ular s inus and conduit network. According to the current paradigm, the conduit network dis tributes afferent lymph through lymph nodes and thus provides acces s for immune cells to lymph-borne antigens. An elas tic caps ule s urrounds the organ and confines the immune cells and FRC network. Lymph nodes are completely packed with lymphocytes and lymphocyte numbers directly dictates the size of the organ. Although lymphocytes cons tantly enter and leave the lymph node, its s ize remains remarkedly s table under homeostatic conditions. It is only partly known how the cellularity and s ize of the lymph node is regulated and how the lymph node is able to swell in inflammation. The role of the FRC network in lymph node s welling and trans fer of fluids are inves tigated in this thes is. Furthermore, we s tudied what trafficking routes are us ed by cancer cells in lymph nodes to form distal metastases.We examined the role of a mechanical feedback in regulation of lymph node swelling. Using parallel plate compression and UV-las er cutting experiments we dis s ected the mechanical force dynamics of the whole lymph node, and individually for FRCs and the caps ule. Physical forces generated by packed lymphocytes directly affect the tens ion on the FRC network and capsule, which increases its resistance to swelling. This implies a feedback mechanism between tis s ue pres s ure and ability of lymphocytes to enter the organ. Following inflammation, the lymph node swells ∼10 fold in two weeks . Yet, what is the role for tens ion on the FRC network and caps ule, and how are lymphocytes able to enter in conditions that resist swelling remain open ques tions . We s how that tens ion on the FRC network is important to limit the swelling rate of the organ so that the FRC network can grow in a coordinated fashion. This is illustrated by interfering with FRC contractility, which leads to faster swelling rates and a dis organized FRC network in the inflamed lymph node. Growth of the FRC network in turn is expected to releas e tens ion on thes e s tructures and lowers the res is tance to swelling, thereby allowing more lymphocytes to enter the organ and drive more swelling. Halt of swelling coincides with a thickening of the caps ule, which forms a thick res is tant band around the organ and lowers tens ion on the FRC network to form a new force equilibrium.The FRC and conduit network are further believed to be a privileged s ite of s oluble information within the lymph node, although many details remain uns olved. We s how by 3D ultra-recons truction that FRCs and antigen pres enting cells cover the s urface of conduit s ys tem for more than 99% and we dis cus s the implications for s oluble information exchangeat the conduit level.Finally, there is an ongoing debate in the cancer field whether and how cancer cells in lymph nodes s eed dis tal metas tas es . We s how that cancer cells infus ed into the lymph node can utilize trafficking routes of immune cells and rapidly migrate to blood vessels. Once in the blood circulation, these cells are able to form metastases in distal tissues.

Re-activation of stem cell pathways for pattern restoration in plant wound healing - Marhavá, Petra; Hörmayer, Lukas; Yoshida, Saiko; Marhavy, Peter; Benková, Eva; Friml, Jiří (Cell)
A process of restorative patterning in plant roots correctly replaces eliminated cells to heal local injuries despite the absence of cell migration, which underpins wound healing in animals. Patterning in plants relies on oriented cell divisions and acquisition of specific cell identities. Plants regularly endure wounds caused by abiotic or biotic environmental stimuli and have developed extraordinary abilities to restore their tissues after injuries. Here, we provide insight into a mechanism of restorative patterning that repairs tissues after wounding. Laser-assisted elimination of different cells in Arabidopsis root combined with live-imaging tracking during vertical growth allowed analysis of the regeneration processes in vivo. Specifically, the cells adjacent to the inner side of the injury re-activated their stem cell transcriptional programs. They accelerated their progression through cell cycle, coordinately changed the cell division orientation, and ultimately acquired de novo the correct cell fates to replace missing cells. These observations highlight existence of unknown intercellular positional signaling and demonstrate the capability of specified cells to re-acquire stem cell programs as a crucial part of the plant-specific mechanism of wound healing.

Targeted cell ablation-based insights into wound healing and restorative patterning - Hörmayer, Lukas; Friml, Jiří (Current Opinion in Plant Biology)
Plants as sessile organisms are constantly under attack by herbivores, rough environmental situations, or mechanical pressure. These challenges often lead to the induction of wounds or destruction of already specified and developed tissues. Additionally, wounding makes plants vulnerable to invasion by pathogens, which is why wound signalling often triggers specific defence responses. To stay competitive or, eventually, survive under these circumstances, plants need to regenerate efficiently, which in rigid, tissue migration-incompatible plant tissues requires post-embryonic patterning and organogenesis. Now, several studies used laser-assisted single cell ablation in the Arabidopsis root tip as a minimal wounding proxy. Here, we discuss their findings and put them into context of a broader spectrum of wound signalling, pathogen responses and tissue as well as organ regeneration.